Fungal Extracellular Vesicles are Recoverable Across Variable Ultracentrifugation Speeds but Display Species-specific Profiles of Sedimentation - Luisa J. Jozefowicz; Bárbara T. Bezerra; Eva Veres; Zóra Szilovics; Cássia M. Souza; Amanda C. Camillo-Andrade; Hellen G. G. Santos; Paulo C. Carvalho; Marlon D. M. Santos; Flavia C. G. Reis; Attila Gacser; Marcio L. Rodrigues (The Journal of Membrane Biology, 2026)

Renal proteomics of male offspring exposed to maternal protein restriction: molecular, epigenetic, and nephron-specific signatures of metabolic programming - Danielle Amanda Niz Alvarez; Isabelle Tenori Ribeiro; Matheus Naia Fioretto; Marina Pereira Pires; Luisa Annibal Barata; Flávia Alessandra Maciel; Luiz Marcos Frediane Portela; Renato Mattos; Hecttor Sebastian Baptista; Pedro Menchini Vitali¹; Vinicius Alexandre Andrade Felipe; Marcel Rodrigues Ferreira; et al. (Journal of Physiology and Biochemistry, 2026)
Chronic kidney disease is an increasing global public health concern, and the Developmental Origins of Health and Disease (DOHaD) concept proposes that adverse conditions during critical developmental windows predispose offspring to chronic disorders later in life. Maternal protein restriction (MPR), a well-established experimental model reflecting food insecurity, has been shown to impair nephrogenesis and promote long-term renal dysfunction. In this study, we investigated renal metabolic–epigenetic programming induced by gestational and lactational MPR in post-weaning male rats using a global kidney proteomic approach. MPR altered renal structure and profoundly dysregulated protein networks, characterized by downregulation of energy metabolism, ion transport, cytoskeletal organization, membrane integrity, and mitochondrial function, alongside upregulation of innate immune pathways, glutathione metabolism, vesicular trafficking, and cytoskeletal dynamics. Integrated pathway and disease enrichment analyses revealed the potential risk to hypertension, acid–base imbalance, renal tubular transport disorders, nephrosis, and renal failure. Key differentially expressed proteins (e.g., GPX1, CYCS, ATP1A2/ATP1B1, TUBB/TUBA isoforms, ANPEP, and metabolic enzymes) emerged as potential biomarkers of renal metabolic–epigenetic programming. Collectively, these findings identify molecular signatures that link early-life protein restriction to long-term risk of kidney disease and provide mechanistic insight into the nephron- and cell-specific consequences of MPR.

Campylobacter jejuni strains isolated in Brazil have important virulence related genes and survive to different stress conditions - Miliane Rodrigues Frazão; Amanda Aparecida Seribelli; Carolina Nogueira Gomes; Giovana do Nascimento Pereira; Guojie Cao; Marta Inês Cazentini Medeiros; Sheila da Silva Duque; Marc William Allard; Juliana Pfrimer Falcão (Brazilian Journal of Microbiology, 2026)
Campylobacter jejuni has been reported as the leading bacterial pathogen that causes foodborne gastroenteritis in humans in many countries. This study aimed to assess the survival of 46 C. jejuni strains isolated from food (14), humans (18), and animals (14) in Brazil from 1996–2016 under different stress conditions, evaluate their invasion and survival capacity in Caco-2 cells and U-937 macrophages and determine virulence using the Galleria mellonella model for 23 selected strains. Furthermore, this study aimed to analyze the frequency of virulence related genes using WGS data. All 46 C. jejuni studied survived to acid stress with survival rates ranging from 29 to 100%. All studied strains survived to incubation in BHI with a final concentration of 7.5% NaCl with survival rates ranging from 3 to 100%. All strains showed growth in the temperatures analyzed with survival rates ranging from 5 to 100% at 4ºC and from 50 to 100% at 37ºC. Only two strains survived after 1 h of incubation under oxidative stress. All strains studied showed the ability to invade Caco-2 cells and to survive in U-937 macrophages. Regarding virulence in G. mellonella , 64% of strains presented virulence equal to or greater than the reference strain. The majority of the virulence genes detected was related to different stress conditions, adhesion, motility, and invasion. In conclusion, the pathogenic potential of the C. jejuni strains studied was highlighted and the results obtained may suggest that more rigorous control measures of this pathogen in food, especially poultry products are needed.

Genotypic and phenotypic characterization of Pseudomonas aeruginosa PAV112: a virulent clinical strain causing severe pneumonia and lethal sepsis in a murine infection model - Raissa Guará Assunção; Beatriz Gomes Vila Nova; Lully Gabrielly Silva Alves; Leticia Cely Tavares da Silva; Gabrielle Chaves Sá; Lucas dos Santos Silva; Marcos Andrade-Silva; Amanda Vitória Sevidanes de Santana; Ivana Fiquene Zafred; Sarah Rackel Silva Soares; Francisco Jonathas Rodrigues Nogueira; Maria Rosa Quaresma Bomfim; et al. (Brazilian Journal of Microbiology, 2026)

Early silicification of continental carbonates: Processes, settings, and implications for the South Atlantic pre-salt - Elias Cembrani; Amanda Goulart Rodrigues; Luiz Fernando De Ros (Earth-Science Reviews, 2026)

First case of canine paraprostatic infection caused by a high-risk ST147 Klebsiella pneumoniae harboring multiple extended-spectrum-β-lactamase genes - Natalia C. Gaeta; Roberto Rodrigues da Rosa Filho; Carine Vieira do Amaral; Willian Seiji Honda; Jéssica Guilhem Alves; Lais Medrado do Nascimento; Carolina de Oliveira Ghirelli; Amanda Haisi; João Pessoa Araújo (Veterinary Research Communications, 2026)
Multidrug-resistant (MDR) Klebsiella pneumoniae , particularly high-risk clones such as sequence type (ST) 147, have been increasingly reported worldwide. However, data on their occurrence in reproductive disorders of companion animals remain limited. This study describes, for the first time, an extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae ST147 isolated from a canine paraprostatic abscess. The isolate (UNISA-DOG-2025) was characterized by antimicrobial susceptibility testing and whole-genome sequencing. Phenotypic analysis revealed an MDR profile, supported by the detection of multiple resistance genes, including β-lactamases ( bla CTX−M−8 , bla CTX−M−15 , bla OXA−1 , bla OXA−9 ), as well as determinants conferring resistance to aminoglycosides, quinolones, sulfonamides, tetracyclines, and trimethoprim. Several of these genes were located on an in silico predicted conjugative IncM1 plasmid, suggesting potential for horizontal dissemination. Phylogenomic analysis demonstrated close relatedness to globally distributed ST147 strains, predominantly associated with human infections. To our knowledge, this is the first report of K. pneumoniae ST147 causing a canine paraprostatic abscess. These findings highlight the clinical relevance of MDR Enterobacterales in canine reproductive disorders and reinforce the need for antimicrobial stewardship and genomic surveillance in veterinary medicine.

Influence of chemotype on the chemical composition, antioxidant activity and in vitro cytotoxicity of Ageratum conyzoides essential oil - Carla Janaina R.M. do Rosário; Amanda M. Teles; Klinger Antonio da F. Rodrigues; Pablo Luis B. Figueiredo; Viviane Correa S. Coimbra; Cláudia Q. da Rocha (South African Journal of Botany, 2026)

Both Bacillus siamensis BACIII inoculation and its carrier medium influence root-associated fungal communities - Jefferson Brendon Almeida dos Reis; Sofia Coradini Schirmer; Alexandra Martins; Chiara Tawane Lauriola; Bianca Rodrigues Teixeira; Geovana Lívio de Macedo; Ana Julia Pereira Rodrigues; Amanda Ribeiro Fernandes de Brito; Vinicius Rodrigues Teodoro; Helson Mario Martins do Vale (Rhizosphere, 2026)

CBD-rich oil nanoemulsion mitigates long-term testicular and endocrine toxicity induced by prenatal valproic acid exposure in rats - Mariana de França Oliveira da Silva; Fernanda Carolina Ribeiro Dias; Amanda Rodrigues dos Santos Magnabosco; Cláudia Kathariny da Silva Farias; Sandra Maria de Torres; Antônio José Alves; Pabyton Gonçalves Cadena; Valdemiro Amaro da Silva Júnior (Reproductive Toxicology, 2026)

Defense-related proteins in Canavalia seeds: Implications for resistance to cowpea weevil Callosobruchus maculatus (F.) - Aline da Gama Melila Licurgo; Sarah Rodrigues Ferreira; Kayan Eudorico Ventury; Roberta Pena da Paschoa; Vanildo Silveira; Thaynã Amanda Melo Souza; Valdirene Moreira Gomes; Antonio Jesus Dorighetto Cogo; Eduardo Atem de Carvalho; Kátia V. Sales Fernandes; Antônia Elenir Amâncio Oliveira (Journal of Stored Products Research, 2026)

Insights on the microbiological quality and safety in Minas artisanal cheese - Caio Fialho de Freitas; Rita de Cássia Vieira Faria; Gabriel Alves Silva de Oliveira; Amanda Rosário Alvim Santos; Rafaela da Silva Rodrigues; Rafaela de Melo Tavares; Anderson Carlos Camargo; Cinzia Caggia; Cinzia Lucia Randazzo; Ricardo Seiti Yamatogi; Antônio Fernandes de Carvalho; Luís Augusto Nero (International Dairy Journal, 2026)

Integrated crop-livestock systems with crop diversification increase soil C and N levels and stocks in subtropical paddy fields in Brazil - Robson Bosa dos Reis; Jakeline Rosa de Oliveira; Cláudia Liane Rodrigues de Lima; Pablo Gerzson Badinelli; Júlio Kuhn da Trindade; Felipe de Campos Carmona; Rogério Oliveira de Sousa; Ibanor Anghinoni; Paulo Cesar de Faccio Carvalho; Amanda Posselt Martins; Cimélio Bayer; Filipe Selau Carlos (Agriculture, Ecosystems & Environment, 2026)

Mechanisms of dyspnoea and exercise intolerance in smokers with preserved ratio impaired spirometry - Alice Scussel; Nathalia Galvagni Rodrigues; Artur Zanelatto Santos; Laura Corrêa de Barros Trombin; Amanda Calage Pinto; Litiele Evelin Wagner; Marli Maria Knorst; James Dean; Dave Singh; Danilo Cortozi Berton (European Journal of Applied Physiology, 2026)
Purpose Smokers with preserved ratio impaired spirometry (PRISm) present reduced forced expiratory volume in the first second (FEV₁ < 80% predicted) but preserved FEV 1 /forced vital capacity (FVC) ≥ 0.7. Although they do not meet diagnostic criteria for chronic obstructive pulmonary disease (COPD), they often report respiratory symptoms and exercise intolerance. We aimed to compare sensory and physiological responses to exercise between smokers with PRISm and matched healthy controls. Patients with mild-to-moderate COPD were included as a reference group. Methods In this cross-sectional study, smokers (> 10 pack-years) from a specialized outpatient clinic were evaluated. Thirteen participants (11 females; 62.4 ± 7.7 years) with PRISm and 13 age- and sex-matched patients with mild-to-moderate COPD (FEV₁/FVC < 0.7; FEV₁ > 50% predicted) underwent incremental cardiopulmonary exercise testing on a cycle ergometer. Data from healthy nonsmoking controls were obtained from previous studies. Results PRISm and COPD groups had similarly reduced FEV₁ (~ 72% predicted) compared to controls (97% predicted), whereas FVC was lower in PRISm (73% predicted) than in COPD and controls (~ 95% predicted). Both patient groups showed higher ventilation, reduced ventilatory reserve, and greater dyspnoea at a given submaximal workload versus controls. Increased tidal volume/inspiratory capacity ratios were also observed, contributing to greater dyspnoea for a given ventilation and lower peak work rate (42 ± 16 vs. 68 ± 11 vs. 94 ± 17% predicted, respectively; all P < 0.05). Conclusion Smokers with PRISm exhibit increased dyspnoea and reduced exercise tolerance compared to healthy controls, largely driven by excessive ventilatory demand and reduced ventilatory capacity during submaximal exercise.

Application of FT-IR spectroscopy using the IR Biotyper® for Leptospira: protocol optimization and first spectral insights - Amanda Maria Jesus Bertani; Elaine Santos Lima; Natalia da Cunha Nobrega; Marcelo Sansone; Juliana Alves Garcia; Daniela Leite; Gisele Oliveira de Souza; Tamires Santos de Arruda; Ricardo Polatto; Eliete Calo Romero; Tania Sueli de Andrade; Karoline Rodrigues Campos; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Central toxic effects of an antitumoral bufadienolide: In silico targets and in vivo findings - Rayran Walter Ramos de Sousa; Antonia Amanda Cardoso de Almeida; Gabriel da Silva Fernandes; Rita de Cassia de Lima Sousa; Railson Pereira Souza; Layana Karine Farias Lima; Francisco das Chagas Pereira de Andrade; Anderson Nogueira Mendes; Evaldo dos Santos Monção Filho; Mariana Helena Chaves; Gerardo Magela Vieira Junior; Domingos de Jesus Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Marinobufagin (MBG), a cardiotonic steroid from Rhinella toads, exhibits potent antitumor activity. However, their involvement in the mammalian neurotoxicity remains unclear. Therefore, this study evaluated the systemic (neuro)toxicological action of MBG to understand its central effects, particularly those associated with seizure-inducing activity. Initially, physicochemical, pharmacokinetic, and drug-likeness profiles and molecular docking with receptors/channels were investigated by in silico platforms. Next, the pro-convulsive action of MBG was investigated using pharmacological modulators for specific neurotransmission pathways and in vitro inhibitory activity of acetylcholinesterase was quantified. MBG has intestinal absorption and capacity to cross the blood–brain barrier (BBB), binds strongly to plasma proteins, and acts as an inhibitory substrate for the CYP3A4 enzyme. It was classified as a drug-like molecule according to Lipinski’s rule and ineligible according to the Lead-like and World Drug Index criteria. Molecular docking emphasized the interaction of MBG with ictogenesis-related targets, confirmed by reduction of in vivo seizures and death of pretreated animals with pharmacological blockers for dopamine D2 and glutamate NMDA receptors and Na v 1.2 channels, mainly. It was shown that affinity of MBG for excitatory targets is essential for neuronal excitability and onset of seizures and that interaction with GABA A receptors is involved in bufadienolide-induced lethality. The findings also suggest that MBG-induced seizures may involve in silico binding to NMDA receptors and interactions with key excitatory (Na v 1.2 channels and NMDA receptor) and inhibitory (GABA A and D2 receptors) neuronal targets, contributing to altered neuronal excitability. Notably, it is the first report that characterized MBG-induced seizures and proposes it as a promising chemical option to understand ictogenesis and mechanism(s) of new anticonvulsive agents.

Antidiabetic activity of Cassia javanica flowers through in vitro inhibitory evaluation of α-amylase, α-glucosidase and its antiglycation property - Íngrede Ferreira Silva; Tarcísio Paiva Mendonça; Matheus Cesar Rodrigues Garcia; Gáveni Barbosa Valério; Allisson Benatti Justino; Foued Salmen Espindola; Amanda Danuello; Marcos Pivatto (Natural Product Research, 2026)

Kaolin-based particle film mitigates high light stress in native tree seedlings through anatomical and growth adjustments - Amanda Lúcia Pereira Machado da Silva; Rosana Maria dos Santos Nani de Miranda; Guilherme Augusto Rodrigues de Souza; Diesily de Andrade Neves; Larissa Crisostomo de Souza Barcellos; Anne Reis Santos; Paulo Ricardo dos Santos; Cláudia Franca Barros; Eliemar Campostrini (Protoplasma, 2026)
Deforestation and environmental degradation increase the need for effective strategies to improve seedling establishment in ecological restoration programs, particularly under high irradiance conditions. Although processed kaolin particle film (PKPF) has been widely used to mitigate abiotic stress in agricultural crops, its potential application to native forest species during restoration remains poorly understood. This study evaluated the effects of PKPF on anatomical, ultrastructural, and biometric traits of Cordia superba and Citharexylum myrianthum , two native Atlantic Forest species commonly used in restoration projects. Seedlings were grown under full sunlight with or without PKPF application and compared with greenhouse-grown plants. PKPF reduced leaf temperature, preserved chloroplast and mitochondrial ultrastructure, and promoted the accumulation of starch grains and plastoglobules. These responses indicate improved maintenance of cellular integrity and energy metabolism under high irradiance, contributing to enhanced stress tolerance during seedling establishment. Growth responses were more pronounced in C. superba , whereas C. myrianthum exhibited greater intrinsic tolerance to light stress. Overall, the results demonstrate that PKPF mitigates the adverse effects of excessive solar radiation by protecting cellular structures associated with photosynthetic performance and supporting seedling development. This study provides novel evidence for the use of kaolin-based technologies in native forest species and highlights their potential to improve restoration success under increasingly challenging environmental conditions.

Assessing coral nursery performance on reefs in Northeast Brazil under bleaching and anthropogenic pressures - Karina Massei; Maria Cecilia Silva Souza; Larissa Fernandes de Lavor; Carlos Alberto Cavalcanti Soares; Márcia Elisabeth Dementshuk; Amanda de Souza Vasconcelos; Patrícia de Moura Almeida; George Emmanuel Cavalcanti de Miranda; Pablo Riul; Frederico Gustavo Rodrigues França; Pedro Costa Guedes Vianna; Celso Augusto Guimarães Santos; et al. (Marine Pollution Bulletin, 2026)

The conodont collection of LACONF at the Institute of Geosciences, UFRGS, Porto Alegre, Brazil - Ana Karina Scomazzon; Andrés Felipe Rojas Mantilla; Martin León Caffroni; Valesca Brasil Lemos; Felipe Medeiros Ceccagno; Everton Wilner; Sara Nascimento; Amanda Pericolo da Rosa; Jordana Maria Viccari; Sanmya Karolyne Rodrigues Dias (Revue de Micropaléontologie, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Bacteriophage-mediated reduction of Pseudomonas aeruginosa biofilm on titanium surfaces for biomedical applications - Amanda Kelly Ferreira Sousa; Viviani Tadioto; Anderson Giehl; Helena Yurevna Caio; Estevão Brasiliense de Souza; Evelin Padilha Corrêa; Mariana Alves Elois; Estevan Rodrigues dos Santos Neto; Sérgio Luiz Alves Junior; Ariadne Cristiane Cabral da Cruz; Mara Cristina Scheffer; Maria Célia da Silva Lanna; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Analysis of the physical and chemical characteristics of stored and fresh Leucaena leucocephala seeds - Viviane da Silva Sousa Almeida; Amanda Graziela Gonçalves Mendes; Tonicley Alexandre da Silva; Daniele Gomes Cassias Rodrigues; Ariadina Jansen Campos Fontes; José Lima Pereira-Filho; Carmem Duarte Lima Campos; Aleania Polassa Almeida Pereira; João Lucas do Carmo Lima; Kátia Danielle Araújo Lourenço Viana; Valério Monteiro-Neto (Food Research International, 2026)

GlyT1 (SLC6A9) inhibition in neurological and psychiatric disorders - Daniel Pereira Cavalcante; Gustavo Almeida Carvalho; Antônio Ítalo Santos Nunes; Amanda Rodrigues Quintanilha; Lucas Rodrigues Couto Nascimento; Leonardo Caixeta; Henning Ulrich; Renato Santiago Gomez; Mauro Cunha Xavier Pinto (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Glycine is a fundamental neuroactive amino acid that serves dual roles in the central nervous system: acting as a primary inhibitory neurotransmitter via strychnine-sensitive glycine receptors and as an essential co-agonist at the N-methyl-D-aspartate (NMDA) receptor. This dual functionality is important for maintaining the excitation–inhibition balance, synaptic plasticity, and network stability. The spatial and temporal availability of glycine is strictly regulated by two high-affinity, Na + /Cl − -dependent transporters: GlyT1 (SLC6A9) and GlyT2 (SLC6A5). These transporters exhibit distinct cellular distributions and functional specializations. GlyT1 is predominantly expressed in astrocytes and specific neuronal populations, where it buffers ambient glycine levels to modulate NMDA receptor activity. In contrast, GlyT2 is primarily localized to presynaptic terminals of glycinergic neurons, where it facilitates vesicular refilling essential for inhibitory signaling. This review provides a comprehensive overview of glycine metabolism, the structural biology and transport cycles of SLC6 glycine transporters, and the neuroanatomical framework of GlyT1 function. We further synthesize pharmacological advances in GlyT1 inhibition, evaluating both sarcosine-derived and non-sarcosine inhibitors, such as NFPS (ALX-5407), bitopertin, and iclepertin. The clinical and preclinical evidence for GlyT1 as a therapeutic target in psychiatric, neurological, and neurodegenerative disorders is critically assessed. Finally, we address key translational challenges, including dosing constraints, compensatory mechanisms, and SLC6 family selectivity, while highlighting the potential of structure-guided design to refine GlyT1-targeted therapies.

Palo Santo (Bursera graveolens) essential oil nanoemulsion: toxicological, antinociceptive and antimicrobial potential against bovine mastitis–associated strains - Amanda Marques Figueiredo; Sabrina Valadão Vilela dos Reis; Alex Alves Rodrigues; Jhuan Luiz Silva; Isabelly Moreira Colombo; Leandra Maria Diniz Batista Leite; João Victor Baldin Neder; Isabela Cristina Gomes Honório; Silvio Almeida-Junior (Antonie van Leeuwenhoek, 2026)
Bovine mastitis is one of the major challenges in dairy production, causing significant economic losses and emphasizing the need for alternatives to the indiscriminate use of antibiotics. Palo Santo ( Bursera graveolens ) essential oil (BEO) presents recognized biological properties that can be enhanced through nanoengineered delivery systems. This study aimed to chemically characterize the BEO of B. graveolens , develop a nanoemulsion containing the essential oil (BEO-NE), and evaluate its toxicological, antinociceptive, and antimicrobial activities against bovine mastitis–associated pathogens. The chemical composition of the BEO was determined by gas chromatography–mass spectrometry (GC–MS), identifying D-limonene (38.70%) as the major constituent. The BEO-NE was formulated using avocado oil as the oil phase and sodium alginate as a stabilizing agent. Toxicological and antinociceptive effects were assessed through in vivo assays, including acute toxicity, acetic acid–induced writhing, and the formalin test. Antimicrobial activity was evaluated by minimum inhibitory and bactericidal concentration assays against Staphylococcus spp., Corynebacterium bovis , Streptococcus uberis , and Prototheca bovis . The BEO-NE showed enhanced antimicrobial activity against Staphylococcus aureus , including MRSA isolates, while exhibiting lower efficacy against C. bovis and S. uberis compared with the free BEO, indicating pathogen-dependent selectivity. The formulation demonstrated a favorable safety profile, with no evidence of hepatotoxicity or behavioral alterations. The BEO also exhibited significant antinociceptive activity, mainly in the neurogenic phase of the formalin test ( p S. aureus , the main etiological agent of bovine mastitis, combining selective antimicrobial and antinociceptive effects.

Alternative strategic control of Rhipicephalus microplus in the Cerrado of Minas Gerais, Brazil, by exploiting abiotic conditions - Vinicius da Silva Rodrigues; Maria Clara Oliveira Sousa; Rodrigo da Costa Maia; Giovanna Cirqueira Ribeiro Borges; Amanda Ferreira Rezende; Ana Carolina Sousa; Gustavo Martins Felix Silva; Adriane Suzin; Matheus Augusto Ferreira Fernandes; Matias Pablo Juan Szabó (Veterinary Parasitology, 2026)

Effects of using a propofol priming and coinduction with ketamine or S(+) Ketamine on the dose of induction and duration of propofol in cats - Vieira Lisiane Saremba; Arboit Francini; Arend Nadine; Souza Andressa Rodrigues; Paraguassú Amanda Oliveira; Oliveira Júlia Odorissi; Biaggio Mario Leite; Rodrigues Ayuá Kaus Harr; Soares André Vasconcelos; Freitas Gabrielle Coelho; Floriano Beatriz Perez (Topics in Companion Animal Medicine, 2026)

Stratigraphic and paleoenvironmental significance of palustrine deposits in bioclastic successions: Morro do Chaves formation, Northeast Brazil - Marila Andrade; Patrick Führ Dal’ Bó; Amanda Rodrigues; Julia Favoreto; Leonardo Borghi; Maurícius Nascimento Menezes (Journal of South American Earth Sciences, 2026)

Detection of Brucella spp. in compost-bedding pack barn and its relationship with infections in dairy cows during the transition period - Marcilene Daniel Damasceno; Maysa Serpa Gonçalves; Maria Eduarda de Souza Teixeira Campos; Amanda Carvalho Rosado Ferreira; Dircéia Aparecida Costa Custódio; Eduarda Moraes Magossi Silva; Vivian Aparecida Malta; Alice Gonçalves dos Reis; Bruno Borges Silva; Ana Clara de Serpa Carvalho; Júlia Lima Paz; Pedro Felipe Rodrigues e Oliveira; et al. (Research in Veterinary Science, 2026)

A Holistic Assessment of Climate Change, Land Use, and Water Governance Through Complex Water Systems - Carolina Stager Quaggio; Lucas Vituri Santarosa; Philip Moffatt; Marcelo Donadelli Sacchi; Bruno Valdambrini; Amanda Rodrigues Soares; Jan Boll; Didier Gastmans (Water Resources Management, 2026)

In vivo genotoxicity and water quality assessment reveal urban influences on the Capibaribe River, Northeastern Brazil - Tyago Henrique Alves Saraiva Cipriano; Jaqueline dos Santos Silva Pinheiro Rodrigues; Livia Caroline Alexandre de Araújo; Iago José Santos da Silva; Aleson Aparecido da Silva; Erima Maria de Amorim; Maria Gislaine Pereira; Lizandra Ferraz da Silva; Eduardo Henrique da Silva Melo; Amanda Alves de Araújo; Anadeje Celerino dos Santos Silva; Elvis Joacir De França; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Encapsulation of jabuticaba (Plinia cauliflora) peel extract with whey or pea protein in combination with gum arabic enhances anthocyanin bioaccessibility and metabolite production - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Janaina Gonçalves Fernandes; Amanda Lais Alves Almeida Nascimento; Hélia de Barros Kobi; Evandro Martins; Pedro Henrique Campelo Felix; Stephen T. Talcottt; Paulo César Stringheta (Food Chemistry, 2026)

Potential activity of paroxetine alone and associated with oxacillin as an alternative to prevent Staphylococcus aureus biofilm formation in catheters - Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Amanda Dias Barbosa; Lara Elloyse Almeida Moreira; Lívia Gurgel do Amaral Valente Sá; Francisca Bruna Stefany Aires do Nascimento; Cecília Rocha da Silva; João Batista de Andrade Neto; Beatriz Oliveira de Souza; Marina Duarte Pinto Lobo; Manoel Odorico de Moraes; Hélio Vitoriano Nobre Júnior (Folia Microbiologica, 2026)

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

Oocyte competence: A systematic review of omics studies and the state of art - Fernanda Amarante Mendes de Oliveira; Gabriela Rodrigues de Paula; Pamela Mara Celestino Soares; Amanda Fonseca Zangirolamo; Fábio Morotti; Anne Kemmer Souza; Fabiana de Andrade Melo-Sterza; Marcelo Marcondes Seneda (Theriogenology, 2026)

Soft-sediment deformation structures in eolian sandstones: Morphology, genesis, and stratigraphical relationships through time - Gabriel Schäffer Sipp; Claiton Marlon Dos Santos Scherer; Amanda Goulart Rodrigues; Ezequiel Galvão De Souza; Rossano Dalla Lana Michel; Monica Oliveira Manna; César Alejandro Goso Aguilar; Fábio Herbert Jones (Sedimentary Geology, 2026)

Exploring the Antimicrobial Potential of a Peptide Against Mixed Biofilm of Staphylococcus aureus and Candida albicans - Graziela Custódia Sandim; Janaina de Cássia Orlandi Sardi; Amanda Carolina Borges da Silva; Leticia Souza Lima; Eduardo Benedetti Parisotto; Edson Crusca Junior; Ana Cristina Jacobowski; Maria Ligia Rodrigues Macedo (Probiotics and Antimicrobial Proteins, 2026)

Unveiling the genomic and phenotypic landscape of Acinetobacter species from different environmental sources in Brazil - Amanda Yaeko Yamada; Anna Luiza Bauer Canellas; Matheus Nunes Diniz; Pedro Smith Pereira Ferraro; Daniel de Sena Miranda; Ana Beatriz Nascimento Costa; Marlon Benedito Nascimento Santos; Karoline Rodrigues Campos; Claudio Tavares Sacchi; Beatriz Balthazar Abdon; Gabrielle da Silva Oliveira Alves; Matheus de Oliveira Nithack Marques; et al. (Antonie van Leeuwenhoek, 2026)

Chemical composition and In Vitro evaluation of the susceptibility of bacterial biofilms to the essential oil of Syzygium cumini (L.) Skeels - José Weverton Almeida-Bezerra; Saulo Almeida Menezes; Adrielle Rodrigues Costa; Janaína Esmeraldo Rocha; Dárcio Luiz de Sousa Júnior; Anna Lídia Nunes Varela; Vinicius Santos Pereira; Marcos Aurélio Figueirêdo dos Santos; Jailson Renato de Lima Silva; Amanda Maria Tavares Moreira; Cicero Dos Santos Leandro; Ademar Maia Filho; et al. (Food and Humanity, 2025)

Impact of silvopastoral shade on thermal stress and conception rates of beef cows in tropical pastures - Amanda Beatriz de Lima Costa; Rafael Henrique Tonissi e Buschinel de Goes; Jefferson Rodrigues Gandra; Gustavo Mafra Fernandes; Gregory Fedri; Lorrayne de Souza Araujo Martins Motta; Antônio Campanha Martinez (Tropical Animal Health and Production, 2025)

Ammoniated sugarcane bagasse associated with forage palm as a replacement for corn in diets for confined lambs - Gabriel Rodrigues Silva Oliveira; Aureliano José Vieira Pires; Raiane Barbosa Mendes; Mateus Pereira Sousa; Willian Nunes Soares; Amanda Ferreira dos Santos; Êmilly Pereira Luz Ferreira; Pedro Henrique Souza Cardoso; Hellen Oliveira Santos; Pedro Paulo Policiano Públio; Fábio Andrade Teixeira (Tropical Animal Health and Production, 2025)

Foliar selenium application mitigates stress induced by El Niño-Southern Oscillation (ENSO) and enhances conilon coffee yield - Edinei José Armani Borghi; Leônidas Canuto dos Santos; Fabrício Teixeira de Lima Gomes; Amanda Santana Chales; Francis Eliakin Portillo Magaña; Maria Ligia de Souza Silva; André Rodrigues dos Reis; Flávio Henrique Silveira Rabêlo; Plinio Rodrigues dos Santos Filho; Marcone Comério; Luiz Roberto Guimarães Guilherme (Plant and Soil, 2025)

Surface Application of Soil Acidity Amendments and Agricultural Gypsum Alter Soil Fertility and Sugarcane Yield - Guilherme Vieira Pimentel; Luiz Daniel Rodrigues da Silva; Silvino Guimarães Moreira; Sérgio Hebron Maia Godinho; Amanda Santana Chales (Journal of Soil Science and Plant Nutrition, 2025)

Nanoemulsion containing 17α-methyltestosterone as a feed additive showed high sex reversal efficiency in Nile tilapia (Oreochromis niloticus) - Matheus Victor Viana de Melo; Amanda Rodrigues dos Santos-Magnabosco; Jadson Freitas da Silva; Aline Rafaely Damaso Alves; Hansheys Ménard; Stefanny Arielle Gomes da Silva; Dijaci Araújo Ferreira; Pabyton Gonçalves Cadena (Aquaculture International, 2025)

Effects of cadmium and lead on the health of white-eared opossums (Didelphis albiventris) in the urban area of Campo Grande/MS, Brazil - Amanda Costa Rodrigues; Filipe Martins Santos; Júlia Aparecida Lima da Mata; Taynara Gabrielly Santos Pinto; Oscar Fernandes Junior; Fernanda Mayara Gauto de Melo; Nayara Yoshie Sano; Valter Aragão Nascimento; Gisele Braziliano de Andrade; Priscila Sabioni Cavalheri; Heitor Miraglia Herrera (Environmental Monitoring and Assessment, 2025)

Structural and functional insights into spermatogenesis and Sertoli cell plasticity in adult common carp (Cyprinus carpio) - Angel Andrés Arias Vigoya; Marcos Antonio Oliveira; Arno Juliano Butzge; Lucas B. Doretto; Amanda de Oliveira Ribeiro; Adriana Carvalho Natal de Moraes; Juliana M.B. Ricci; Maira da Silva Rodrigues; Ivana Felipe Rosa; Diógenes Henrique de Siqueira-Silva; Rafael Henrique Nóbrega (Theriogenology, 2025)

Trans-chalcone affects schistosomula and adult worms by impairing membrane integrity and attenuates the effects of Schistosoma mansoni-induced liver fibrosis - Mariana Barbosa Detoni; Luryan Silvério Fidélis Ortiz; Amanda Caroliny Gomilde; Bruna Taciane da Silva Bortoleti; Fernanda Tomiotto-Pellissier; Virgínia Marcia Concato-Lopes; Manoela Daiele Gonçalves-Lens; Taylon Felipe Silva; Ana Carolina Jacob Rodrigues; Amanda Cristina Machado Carloto; Ellen Mayara Souza Cruz; Danielle Lazarin-Bidóia; et al. (Chemico-Biological Interactions, 2025)

Contamination by microplastics in free-living white-eared opossums (Didelphis albiventris) resident in Campo Grande, Mato Grosso do Sul, Brazil - Fernanda Mayara Gauto de Melo; Heitor Miraglia Herrera; Amanda Costa Rodrigues; Oscar Fernandes Junior; Filipe Martins Santos; Taynara Gabrielly Santos Pinto; Wesley Arruda Gimenes Nantes; Nayara Yoshie Sano; Priscila Sabioni Cavalheri; Gisele Braziliano de Andrade (Environmental Monitoring and Assessment, 2025)

Bioactive withanolides from the leaves of Athenaea velutina (Sendtn.) D'Arcy - Késya Amanda Dantas Rocha; Edilberto Rocha Silveira; Tércio de Freitas Paulo; Alejandro Pedro Ayala; Bruno Marques Soares; Sarah Sant’Anna Maranhão; Cláudia do Ó Pessoa; Iury Araújo Paz; Maria Lidia Barroso Rodrigues; Nilberto Robson Falcão do Nascimento; Kirley Marques Canuto; Otília Deusdenia Loiola Pessoa (Phytochemistry, 2025)

Whey protein and probiotic supplementation ameliorates DSS-induced colitis in mice - Amanda Ascanio; Jaqueline Cristina Galiardo; Eliane Vale da Silva; José Antônio Sampaio Zuanon; Luis Carlos Spolidorio; Letícia de Aquino Penteado; Priscila Marques Firmiano Dalle Piagge; José Fernando Rinaldi de Alvarenga; Alexandra Ivo de Medeiros; Daniel Rodrigues Cardoso; Daniela Cardoso Umbelino Cavallini (International Dairy Journal, 2025)

Baru (Dipteryx alata Vog.) by-product following gastrointestinal digestion: bioaccessibility, antioxidant capacity and in vitro effects on inflammatory response of phenolic compounds - Daniela Canuto Fernandes; José Rodrigues do Carmo Neto; Amanda de Oliveira Matos; Marcos dos Santos Lima; Helioswilton Sales-Campos; Maria Margareth Veloso Naves (Food Research International, 2025)

Processed-kaolin particle film can mitigate solar radiation damage in young Atlantic Forest species - Amanda Lúcia Pereira Machado da Silva; Guilherme Augusto Rodrigues de Souza; Rosana Maria dos Santos Nani de Miranda; Diesily de Andrade Neves; Larissa Crisostomo de Souza Barcellos; Silas Magno Medeiros Garonce; Moises de Souza Marcelino; Newton de Matos Roda; Paulo Ricardo dos Santos; Cláudia Franca Barros; Eliemar Campostrini (Trees, 2025)

Effects of Lacticaseibacillus rhamnosus LB1.5 as potential probiotic supplement on the liver and adipose tissue of adult male mice to a high-fat diet - Natália Perin Schmidt; Milena Henrique Ferri; Patrícia Molz; Brenda Santos Fraga; Priscila Dutra Silveira; Daiana Rodrigues dos Santos; Juan Andres Cuadro Montanez; Gabriela Merker Breyer; Amanda de Souza da Motta; Marilene Porawski; Alethea Gatto Barschak; Renata Padilha Guedes; et al. (Molecular and Cellular Biochemistry, 2025)

Antibacterial potential of antidepressants against extended-spectrum β-lactamase-producing Escherichia coli - Cecília Rocha da Silva; Lívia Gurgel do Amaral Valente Sá; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Lara Elloyse Almeida Moreira; Érica Rayanne Mota da Costa; Thais Lima Ferreira; Maria Janielly Castelo Branco Silveira; Tatiana do Nascimento Paiva Coutinho; Letícia Bernardo Barbosa; Igor Gomes Aguiar; Bruno Coêlho Cavalcanti; et al. (Folia Microbiologica, 2025)

Antibacterial activity of diazepam against planktonic and biofilm strains of methicillin-resistant Staphylococcus aureus - Thaís Lima Ferreira; Lívia Gurgel do Amaral Valente Sá; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Lara Elloyse Almeida Moreira; Beatriz Oliveira de Souza; Bruno Coêlho Cavalcanti; Hemerson Iury Ferreira Magalhães; Iri Sandro Pampolha Lima; Amanda Cavalcante Leitão; Manoel Odorico de Moraes; João Batista de Andrade Neto; et al. (Biofouling, 2025)

Histological alterations in placentas of normal and anomalous pups: correlation with neonatal outcomes and fetal health - Laura M. Lovo; Marina Vilela Estevam; Samara Beretta; Amanda Marmol; Loren M. Pasqui; Fernanda A. Rodrigues-Silva; Renata O. Barreto; Alessandre Hataka; Gilson Hélio Toniollo; Maria Lúcia G. Lourenço; Maricy Apparício (Theriogenology, 2025)

How do visitors perceive the urban greenery microclimate in the city’s only green space? A case study in Brazilian semi-arid - Arthur da Silva Nascimento; Leonardo Vitor Alves da Silva; Maria Amanda Nobre Lisboa; Alana de Oliveira Silva; Mardonio Freitas Rodrigues Ferreira; Sara Cardoso Ferreira da Silva; Mário Jorge Vital de Melo; Antônio César Vieira da Silva; João Tavares Calixto Júnior (Environmental Development, 2025)

Exploring the annual seasonal impacts on the ecological restoration of post-mining sites - Rugana Imbaná; Fernanda Daniele de Almeida Valente; Maísa Quintiliano Alves; Sandro Lucio Silva Moreira; Fernanda Zeidan Oliveira; Amanda de Abreu Anunciação; Rosilene Rodrigues Silva; Felipe Tadashi Asao Coelho; Igor Rodrigues de Assis (Ecological Engineering, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Clinical and pathological characterization of a feline intestinal large granular lymphocyte lymphoma (LGLL) - Camila Issa Amaral; Lorena Santos Bezerra; Acácia Eduarda de Jesus Nascimento; Nayara Toledo da Silva; Lize Amanda Basaglia Borges; Paloma Helena Sanches da Silva; Letícia Monteiro Barbosa; Anelise Carvalho Nepomuceno; Rodrigo dos Santos Horta; Geovanni Dantas Cassali; Ayisa Rodrigues Oliveira (Veterinary Research Communications, 2025)

Herbicide selectivity and efficacy in weed control in canola production system - Natalia Costa; Guilherme Vieira Pimentel; Amanda Santana Chales; Luiz Daniel Rodrigues da Silva; Elisabete da Cruz Silva Watanabe; Adenilson Henrique Gonçalves (Crop Protection, 2025)

The early Aptian marine stratigraphic record in the interior of Gondwana: New insights from the Araripe Basin, Northeastern Brazil - Henrique Parisi Kern; Jorge Villegas-Martín; Gerson Fauth; Fernanda Luft-Souza; Oscar Strohschoen; Lilian Maia Leandro; Alessandra Santos; Mauro Daniel Rodrigues Bruno; Edna de Jesus Francisco Tungo; Marcos Antonio Batista dos Santos Filho; Daiane Ceolin; Simone Baecker-Fauth; et al. (Marine and Petroleum Geology, 2025)

Impact of housing in stalls vs. pens on productivity and semen quality of boars - Alisson Leandro Ansolin; Natan Augusto de Souza Viana; Ygor Faria Nagano; Romário Alencar Oliveira; Rosiel Moreira Cavalcante Filho; Luis Candido Alvez Rodrigues; Amanda Pimenta Siqueira (Animal Reproduction Science, 2025)

Deregulation of Neuroinflammatory and Neurotrophic Factors as Biological Events Triggered by D-Galactose Chronic Administration in Wistar Rats - Eduarda Behenck Medeiros; Sabrina da Silva; Francielle Mina; Adrielly Vargas Lidio; Amanda Boaventura; Laura Ceolin de Jesus; Michelle Lima Garcez; Gabriel Casagrande Zabot; Gabriela Piovesan Fenilli; Matheus Scarpatto Rodrigues; Jade de Oliveira; Samira S. Valvassori; et al. (NeuroMolecular Medicine, 2025)

Short communication: Effects of age on the immune response induced by Brucella abortus S19 or RB51 vaccination in calves - Maysa Serpa Gonçalves; Marina Martins de Oliveira; Eduarda Moraes Magossi Silva; Lorena Batalha de Souza; Rafaella Silva Andrade; Dircéia Aparecida da Costa Custódio; Amanda Carvalho Rosado Ferreira; Anna Cecília Trolesi Reis Borges Costa; Helbert Resende Freire; Carine Rodrigues Pereira; Izabela Regina Cardoso de Oliveira; Júlio Silvio de Sousa Bueno Filho; et al. (Veterinary Immunology and Immunopathology, 2025)

Oral supplementation of probiotic blends for low and high birth weight piglets - Amanda Rodrigues Fernandes; Dayanne Kelly Oliveira Pires; Soraia Viana Ferreira; Guilherme de Moraes Chaves; Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Luisa Lopes da Rocha dos Santos; Dalton de Oliveira Fontes (Tropical Animal Health and Production, 2025)

Nitrogen Modifies the Leaf Anatomy and the Antioxidant System of Cotton in Irrigated and Rainfed Cultivation - Amanda Pereira Paixão-Daruichi; Enes Furlani Junior; Liliane Santos de Camargos; Ricardo Antonio Ferreira Rodrigues; Thalissa Cagnin Pereira; Mariana Monteiro de Lima Honorato Forini; Dayane Bortoloto da Silva; Noemi Cristina de Souza Vieira; Raiana Crepaldi de Faria Nocchi; Carlos Eduardo da Silva Oliveira; Aline Redondo Martins (Journal of Plant Growth Regulation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Comparative study of trends in photosynthetic metabolism knowledge between Brazil and the United States - Amanda Maria Tavares Moreira; Jailson Renato de Lima Silva; Patric Anderson Gomes da Silva; Carlos Alonso Leite dos Santos; Bárbara Rayanne da Silva Teles; Adrielle Rodrigues Costa; Elizângela Beneval Bento; Waseem Hassan; Jean Paul Kamdem; Luiz Marivando Barros; Antonia Eliene Duarte (Vegetos, 2025)

Prediction of marbling score in ribeye quartered at the 5th- 6th rib of French beef using the Q-FOM™ beef assessment camera - Nathalia da Silva Rodrigues Mendes; Mette Christensen; Moïse Kombolo-Ngah; Pascal Faure; Laure Thoumy; Alix Neveu; Amanda Gobeti Barro; Jingjing Liu; Tatianne Ferreira de Oliveira; Marie-Pierre Ellies-Oury; Sghaier Chriki; Jean-François Hocquette (Meat Science, 2025)

Lactobacillus rhamnosus Modulates Lung Inflammation and Mitigates Gut Dysbiosis in a Murine Model of Asthma-COPD Overlap Syndrome - Jéssica Aparecida Vasconcelos; Amanda Sodre Mota; Fabiana Olímpio; Paloma Cristina Rosa; Nilsa Damaceno-Rodrigues; Rodolfo de Paula Vieira; Carla Romano Taddei; Flavio Aimbire (Probiotics and Antimicrobial Proteins, 2025)

(Bio)Hybrid System of Layered Double Hydroxides and Dapsone: One-Pot Synthesis, Structural Characterization and Cell Viability - Felipe de Albuquerque Marinho; Amanda Damasceno Leão; Antônia Carla de Jesus Oliveira; Luise Lopes Chaves; Jessica Cavalcante Martins; Izabel Maria de Melo Amaral; Mylena Karolina Oliveira Do Amaral; Lucas José de Alencar Danda; Raiza Raianne Luz Rodrigues; Rafael Alexandre Raimundo; Klinger Antonio da Franca Rodrigues; Mônica Felts de La Rocca Soares; et al. (Journal of Pharmaceutical Innovation, 2025)

Bioprospecting of Trichoderma strains for controlling pathogens from soybean, maize, and beans, and their microbiome characterization - Amanda Oliveira Rodrigues; André Luiz Graf Junior; Thiago de Aguiar Carraro; Brigitte Sthepani Orozco Colonia; Louise Larissa May De Mio; Carlos Ricardo Soccol (European Journal of Plant Pathology, 2025)

Non‐Native Species Abundance Decreases the Co‐Occurrence Between Native and Non‐Native Species Through Time at Any Phylogenetic Distance - Amanda Cantarute Rodrigues; Rafaela Vendrametto Granzotti; Natália Carneiro Lacerda dos Santos; Angelo Antonio Agostinho; Luiz Carlos Gomes (Ecology Letters, 2025)
Non‐native species may cause cumulative impacts on native communities if their abundance continues to increase through time. This negative effect can reflect on the spatial distribution of native species, especially when native and non‐native species are phylogenetically similar. Here, we assessed the spatial co‐occurrence between native and non‐native fish species using long‐term abundance data from six locations in a Brazilian floodplain. We tested whether the co‐occurrence of native and non‐native species is influenced by non‐native species abundance and time since first record, and whether the abundance effect is mediated by the phylogenetic relatedness between native and non‐native species. We found that non‐native abundance was more influential than the time since first record and co‐occurrence between native and non‐native species was lower when the non‐native abundance was high, regardless of phylogenetic relatedness. The interannual variability in non‐native species abundance may overshadow long‐term trends in determining the temporal effects of non‐native species.

Brazilian Green Propolis Extract-Loaded Poly(Ε-Caprolactone) Nanoparticles Coated with Hyaluronic Acid: Antifungal Activity in a Murine Model of Vulvovaginal Candidiasis - Aniely Dos Reis Teixeira; Amanda De Vasconcelos Quaresma; Renata Tupinambá Branquinho; Patrícia Capelari De Oliveira; Jorge Andrés García Suárez; Geraldo Célio Brandão; Ana Paula Moreira Barboza; Marcelo Gonzaga De Freitas Araújo; Juliana Teixeira De Magalhães; Sandra Aparecida Lima De Moura; Gisele Rodrigues Da Silva (AAPS PharmSciTech, 2025)

Retraction notice to “The exposure in ovo of embryos belonging to Amazonian turtle species Podocnemis expansa (Testudines) to commercial glyphosate and fipronil formulations impairs their growth and changes their skeletal development” [Sci. Total Environ. 842 (2022) 156709] - Juliana dos Santos Mendonça; Líria Queiroz Luz Hirano; André Luiz Quagliatto Santos; Daniela de Melo e Silva; Carolina de Castro Pereira; Matheus Santos Costa; Phâmella Neres de Lima; Amanda Pereira da Costa Araújo; Guilherme Malafaia; Isabela Sayuri Ambrósio; Lais de Moura Bife Castilho; Allyson Leandro Rodrigues dos Santos; et al. (Science of The Total Environment, 2025)

Antimicrobial activity and insecticidal evaluation of Passiflora edulis Sims. (Passifloraceae) - Adrielle Rodrigues Costa; Saulo Almeida Menezes; José Weverton Almeida-Bezerra; Severino Denicio Gonçalves de Sousa; Dhenes Ferreira Antunes; Elaine Cristina Conceição de Oliveira; Janaína de Souza Bezerra; Dieferson Leandro de Souza; Eveline Naiara Nuvens Oliveira; Francisca de Fátima Silva de Sousa; Maria Aparecida Barbosa Ferreira Gonçalo; Germana de Alencar Maia Luz; et al. (Vegetos, 2025)

Prospecting the Functional Potential of Bacillus altitudinis 1.4 Isolated from Sediment in Association with Bradyrhizobium japonicum - Priscila Ribeiro Jankoski; Evelise Bach; Daniela Ritiele Quadros Bald; Luciane Maria Pereira Passaglia; Joseane Biso de Carvalho; Rafael Rodrigues de Oliveira; Wellington Pine Omori; Amanda de Souza da Motta (Current Microbiology, 2025)

Chemical composition and influence of essential oil from Croton pulegiodorus Baill. Leaves on the nutrition and survival of Sitophilus zeamais Mots. (Coleoptera: Dryophthoridae) as well as survival and behavior of Nasutitermes corniger Mots. (Blattodea: Termitidae) - Patryck Érmerson Monteiro dos Santos; Thiago Henrique Napoleão; Amanda Vieira de Barros; Renata Mendonça Araújo; Matheus Cavalcanti de Barros; Carlos Romero Ferreira de Oliveira; Maria Betânia Melo de Oliveira; Maria Lígia Rodrigues Macedo; Ana Patrícia Silva de Oliveira; Thâmarah de Albuquerque Lima; Patrícia Maria Guedes Paiva (Crop Protection, 2025)

Comparative effects of Serendipita indica and a mix of arbuscular mycorrhizal fungi on the growth, photosynthetic capacity, and proteomics of Schinus terebinthifolius Raddi - Amanda A. Bertolazi; Lucas Z. Passamani; Sávio B. de Souza; Weverton P. Rodrigues; Eliemar Campostrini; Vitor B. Pinto; Vanildo Silveira; Carlos E. de Rezende; Cristina Cruz; Elke J. B. N. Cardoso; Alessandro Coutinho Ramos (Planta, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Recovery of health-promoting phenolic compounds from clove basil (Ocimum gratissimum L.) by aqueous extraction and ultrafiltration - Kristopher Rodrigues Dorneles; Amanda Carmelo da Rocha; Vicelma Luiz Cardoso; Miria Hespanhol Miranda Reis (Food and Bioproducts Processing, 2025)

Utilization of biodiesel residue through efficient microwave-assisted synthesis of carbon quantum dots: A versatile nanomaterial for environmental remediation - Carolina Inácio Portela; Nirton Cristi Silva Vieira; Tayra Rodrigues Brazil; Amanda Soares Giroto; José Balena Gabriel Filho; Maraísa Gonçalves (Environmental Research, 2025)

Potential Mechanisms Underlying COVID-19-Mediated Central and Peripheral Demyelination: Roles of the RAAS and ADAM-17 - Kellysson Bruno Oliveira; Fernanda Maria Araujo de Souza; Letícia Barros Maurício de Sá; Amanda Larissa Dias Pacheco; Mariana Reis Prado; Célio Fernando de Sousa Rodrigues; Ênio José Bassi; Igor Santana-Melo; Abelardo Silva-Júnior; Robinson Sabino-Silva; Ashok K. Shetty; Olagide Wagner de Castro (Molecular Neurobiology, 2025)

Correlation between ultrasound evaluation of the prostate and age, weight, kinetics and sperm morphology of German Spitz breeders - Bruno Alcantara Buzato; Luiz Guilherme Corsi Trautwein; Myrian Megumy Tsunokawa Hidalgo; Leticia Amanda dos Santos Silva; Julia Rodrigues Greghi; Vinicius Wagner Silva; Natalia Ribeiro Sambatti; Maria Isabel Mello Martins (Animal Reproduction Science, 2025)

Retraction notice to “Ingestion of tannery effluent as a risk factor to the health of birds: A toxicological study using Coturnix coturnix japonica as a model system” [Science of the Total Environment 681 (2019) 275–291] - Douglas Marcel dos Reis Sampaio; Fernanda Neves Estrela; Bruna de Oliveira Mendes; Dieferson da Costa Estrela; Mateus Flores Montalvo; Carlos Mesak; Fabiano Guimares Silva; Amanda Pereira da Costa Arajo; Carla Santos de Freitas; Boniek Vaz Gontijo; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “How leachates from wasted cigarette butts influence aquatic life? A case study on freshwater mussel Anodontites trapesiali” [Sci. Total Environ. 689 (2019) pages 381–389] - Mateus Flores Montalvão; Thales Quintão Chagas; Tenilce Gabriela da Silva Alvarez; Carlos Mesak; Amanda Pereira da Costa Araújo; Alex Rodrigues Gomes; Julya Emmanuela de Andrade Vieira; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “Toxicity assessment of SARS-CoV-2-derived peptides in combination with a mix of pollutants on zebrafish adults: A perspective study of behavioral, biometric, mutagenic, and biochemical toxicity” [Sci. Total Environ. 858 Part 2 (2023) 159838] - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Amanda Pereira da Costa Araújo; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Alex Rodrigues Gomes; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Andrés Hugo Arias; Davoodbasha Mubarak Ali; Chinnasamy Ragavendran; et al. (Science of The Total Environment, 2024)

Retraction notice to “Short-term exposure of the mayfly larvae (Cloeon dipterum, Ephemeroptera: Baetidae) to SARS-COV-2-derived peptides and other emerging pollutants: A new threat for the aquatic environments” [Sci. Total Environ. 849 (2022) 157813] - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Nabisab Mujawar Mubarak; Md. Mostafizur Rahman; Andrés Hugo Arias; Guilherme Malafaia (Science of The Total Environment, 2024)

Active biodegradable film with garlic essential oil: From elaboration to cytotoxicity and preliminary assessment of antibiotic resistance in Staphylococcus aureus - Clara Suprani Marques; Tarsila Rodrigues Arruda; Marcus Tulio Cunha dos Santos Filho; Amanda Camilo Graciano; Kamilla Soares de Mendonça; Bianca Muniz Lacerda Ventura; Amanda Lelis de Souza; Taíla Veloso de Oliveira; Tiago Antônio de Oliveira Mendes; Nilda de Fátima Ferreira Soares (Food Control, 2024)

Ensuring authenticity of cinnamon powder: Detection of adulteration with coffee husk and corn meal using NIR, MIR spectroscopy and chemometrics - Jéssica Souza Coqueiro; Amanda Beatriz Sales de Lima; Josane Cardim de Jesus; Robério Rodrigues Silva; Sibelli Passini Barbosa Ferrão; Leandro Soares Santos (Food Control, 2024)

Enhancement of phenolic compounds bioaccessibility in jabuticaba wine through fermentation by Saccharomyces cerevisiae - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Amanda Lais Alves Almeida Nascimento; Janaina Gonçalves Fernandes; Hélia de Barros Kobi; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Luciana Ângelo de Souza; Gabriel Abranches Dias Castro; Arthur Figueira de Carvalho; Jaqueline de Araújo Bezerra; Sergio Antonio Fernandes; et al. (Food and Bioproducts Processing, 2024)

Cytogenetics and DNA barcode in Hoplias gr. malabaricus (Characiformes, Erythrinidae) reveals correlation between karyomorphs and valid species - Diana Paula Perin; Denise Felicetti Máh; Chrystian Aparecido Grillo Haerter; Sandro Tonello; Amanda de Souza Machado; Leonardo Marcel Paiz; Maelin da Silva; Luciana Borowski Pietricoski; Dalila Moter Benvegnú; Vladimir Pavan Margarido; Daniel Rodrigues Blanco; Roberto Laridondo Lui (Reviews in Fish Biology and Fisheries, 2024)

Ascophyllum nodosum-derived biostimulant promotes physiological conditioning to increase soybean yield in a semiarid climate - Jeane Ferreira de Jesus; Amanda Soares Santos; Renato Oliveira de Sousa; Bruno Sousa Figueiredo da Fonseca; Wesley Santos Ferreira; Rodrigo Fonseca da Silva; Stelamaris de Oliveira Paula-Marinho; Priscila Alves Barroso; Milena Rodrigues Luz; Francisco de Alcântara Neto; José Hélio Costa; Rafael de Souza Miranda (Journal of Applied Phycology, 2024)

Antifungal and antibiofilm effect of duloxetine hydrochloride against Cryptococcus neoformans and Cryptococcus gattii - Amanda Rodrigues Rehem; Letícia Rampazzo da Gama Viveiro; Evelyn Luzia De Souza Santos; Paulo Henrique Fonseca do Carmo; Newton Soares da Silva; Juliana Campos Junqueira; Liliana Scorzoni (Folia Microbiologica, 2024)

Unveiling novel insights: geraniol’s enhanced anti-candida efficacy and mechanistic innovations against multidrug-resistant candida strains - Lisandra Juvêncio da Silva; Daniel Sampaio Rodrigues; Vitória Pessoa de Farias Cabral; Cecília Rocha da Silva; Lívia Gurgel do Amaral Valente Sá; João Batista de Andrade-Neto; Amanda Dias Barbosa; Amanda Arrais Flaresso; Sânia Nara Costa da Rocha; Bruno Coelho Cavalcanti; Manoel Odorico de Moraes; Maria Erivanda França Rios; et al. (Brazilian Journal of Microbiology, 2024)

The GC% landscape of the Nucleocytoviricota - Amanda Stéphanie Arantes Witt; João Victor Rodrigues Pessoa Carvalho; Mateus Sá Magalhães Serafim; Nidia Esther Colquehuanca Arias; Rodrigo Araújo Lima Rodrigues; Jônatas Santos Abrahão (Brazilian Journal of Microbiology, 2024)

Antifungal activity of tannic acid against Candida spp. and its mechanism of action - Lara Elloyse Almeida Moreira; Vitória Pessoa de Farias Cabral; Daniel Sampaio Rodrigues; Amanda Dias Barbosa; Maria Janielly Castelo Branco Silveira; Tatiana do Nascimento Paiva Coutinho; Sarah Alves Barbosa; Lívia Gurgel do Amaral Valente Sá; João Batista de Andrade Neto; Sania Nara Costa da Rocha; Celina Santos Reis; Bruno Coelho Cavalcanti; et al. (Brazilian Journal of Microbiology, 2024)

Long-term sustainability of the water-agriculture-energy nexus in Brazil’s MATOPIBA region: A case study using system dynamics - Minella Alves Martins; David Collste; Francisco Gilney Silva Bezerra; Marcela Aparecida Campos Neves Miranda; André Rodrigues Gonçalves; Jocilene Dantas Barros; Manoel Ferreira Cardoso; Amanda Sousa Silvino; Taís Sonetti-González; Jean Pierre Henry Balbaud Ometto; Celso von Randow; Javier Tomasella; et al. (Ambio, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Berthierine/Chamosite ooids and associated phases in Devonian deposits of the Parnaíba Basin, Brazil: Genesis and diagenetic evolution - Matheus Moreira Schirmbeck; Amanda Goulart Rodrigues; Leonardo Borghi; Luiz Fernando De Ros (Journal of South American Earth Sciences, 2024)

Pennsylvanian epicontinental sea dynamics in Western Gondwana: Stratigraphic, petrographic, and C, O, and Sr isotopic insights from the Itaituba Formation, Amazonas Basin - Maria D. Traslaviña-Bueno; Juliana C. Marques; Afonso C. Nogueira; Pedro A. Silva; Juan S. Gomez-Neita; Amanda G. Rodrigues; André A. Martins; Paulo A. Souza; Ana K. Scomazzon; Marcia E. Longhim (Journal of South American Earth Sciences, 2024)

Mesoproterozoic siliciclastic stromatolites of Chapada Diamantina (Brazil): Morphological types, genesis and environmental context - João Pedro Formolo Ferronatto; Claiton Marlon dos Santos Scherer; Bruno Silverstone Angonese; Amanda Goulart Rodrigues; Ezequiel Galvão de Souza; Carrel Kifumbi; Adriano Domingos dos Reis; Felipe Guadagnin; Caroline Lessio Cazarin (Journal of South American Earth Sciences, 2024)

First report of angular leaf spot in Acmella oleracea caused by the foliar nematode Aphelenchoides pseudobesseyi - Marcela de Freitas Silva; Felipe Castro Faccioli; Amanda Pereira Honório; Andressa Rodrigues Fonseca; Alessandra de Jesus Boari; Cláudio Marcelo Gonçalves de Oliveira; Dalila Sêni Buonicontro (Journal of Plant Diseases and Protection, 2024)

VARI as an indicator of site productivity of Pinus taeda L.: soil, litter, and plant nutrition - Tamires Maiara Ercole; João Bosco Vasconcellos Gomes; Valdécio dos Santos Rodrigues; Nicolas dos Santos Trentin; Jairo Calderari de Oliveira Junior; Gabriel Assis-Pereira; Mario Tomazello-Filho; Amanda Pacheco Cardoso Moura; Shizuo Maeda; Stephen Arthur Prior; Rangel Consalter; Antônio Carlos Vargas Motta (European Journal of Forest Research, 2024)

Aquatic hyphomycetes associated with plant debris in freshwater ecosystems of the Atlantic Forest of Rio Grande do Norte, Brazil - Heloysa Farias da Silva; Amanda Regis Assunção; Douglas de Souza Braga Aciole; Flavia Rodrigues Barbosa; Patrícia Oliveira Fiuza (New Zealand Journal of Botany, 2024)

Three-dimensional geological modeling applied to multiscale heterogeneity of a reservoir analog: Paleocoastal deposits from the Rio Bonito formation, Paraná Basin - Ricardo Maahs; Juliano Kuchle; Amanda Goulart Rodrigues; Mariane Cristina Trombetta; Renata dos Santos Alvarenga; Rosalia Barili; William Freitas (Marine and Petroleum Geology, 2024)

Green banana (Musa ssp.) mixed pulp and peel flour: A new ingredient with interesting bioactive, nutritional, and technological properties for food applications - Leonara Martins Viana; Fabiana Silva Rocha Rodrigues; Millena Cristina Barros Santos; Amanda dos Santos Lima; Elizabeth Harumi Nabeshima; Mauricio de Oliveira Leite; Márcio Arêdes Martins; Carlos Wanderlei Piler de Carvalho; Vinícius Gonçalves Maltarollo; Luciana Azevedo; Mariana Simões Larraz Ferreira; Hércia Stampini Duarte Martino; et al. (Food Chemistry, 2024)

Morpho-anatomical adaptations of Centella asiatica (Apiaceae) in different coastal sand microenvironments of Restinga and in an urbanized area - Calebe Borges; Makeli Garibotti Lusa; Amanda Baldessar; Guilherme Almeida Garcia Rodrigues; Ana Claudia Rodrigues (Flora, 2024)

The Antidepressant- and Anxiolytic-Like Effects of the Phosphodiesterase Type-5 Inhibitor Tadalafil are Associated with the Modulation of the Gut-Brain Axis During CNS Autoimmunity - Eduardo Duarte-Silva; Alice Chevrollier Oriá; Ingrid Prata Mendonça; Igor Henrique Rodrigues Paiva; Klyvia Leuthier dos Santos; Amanda Juliana Sales; José Roberto Botelho de Souza; Michael Maes; Sven Guenther Meuth; Christina Alves Peixoto (Journal of Neuroimmune Pharmacology, 2024)

Intake, digestibility, serum metabolites, and growth performance of male feedlot lambs fed different fat sources - Henry D.R. Alba; José E. de Freitas; Laudí C. Leite; José A.G. Azevêdo; Stefanie A. Santos; Douglas dos S. Pina; Luis G.A. Cirne; Carlindo S. Rodrigues; Manuela S.L. Tosto; Silvia C. Bento; Amanda B. Grimaldi; Gleidson G.P. de Carvalho (Livestock Science, 2024)

Paraná basin basalt powder: A multinutrient soil amendment for enhancing soil chemistry and microbiology - Marlon Rodrigues; Lucas Francisco da Silva Junges; Claiane Mozorovicz; Guilherme Seidel Ziemmer; Carlos Kosera Neto; Ederson Américo de Andrade; Amanda Izabel dos Passos; Fábio Palczewski Pacheco; Everson Cezar; Leticia de Melo Teixeira (Journal of South American Earth Sciences, 2024)

How do replanted mangroves affect phosphorus dynamics in their soils? - Gabriela Rodrigues da Silva; Marcela Lopes Lázaro; Hermano Melo Queiroz; Amanda Duim Ferreira; Rut Amelia Díaz Ramos; Wilson Thadeu Valle Machado; Xosé L. Otero; Tiago Osório Ferreira; Gabriel Nuto Nóbrega (Journal of Environmental Management, 2024)

Potential of drying carrot using ozone pre-treatment: Mass transfer modelling and techno-functional properties - Newton Carlos Santos; Raphael Lucas Jacinto Almeida; Shênia Santos Monteiro; Eduardo Wagner Vasconcelos de Andrade; Maria Monique Tavares Saraiva; Thalis Leandro Bezerra de Lima; Amanda Priscila da Silva Nascimento; Francisca Moisés de Sousa; Raniza de Oliveira Carvalho; Mailson Gonçalves Gregório; Thaís Jaciane Araújo Rodrigues; Michael Marcos de Aquino Gomes; et al. (Food and Bioproducts Processing, 2024)

Potential of integrated trees-pasture-based systems for GHG emission mitigation and improving soil carbon dynamics in the Atlantic forest biome, Southeastern of Brazil - Patrícia Perondi Anchão Oliveira; Alberto Carlos Campos Bernardi; José Ricardo Macedo Pezzopane; Cristiam Bosi; Flávio Perna Júnior; Amanda M. Tadini; Ladislau Martin-Neto; Paulo Henrique Mazza Rodrigues (European Journal of Agronomy, 2024)

Functional dissimilarity correlates to the co-occurrence patterns of native and non-native species - Amanda Cantarute Rodrigues; Julien Cucherousset; Eduardo Ribeiro Cunha; Natália Carneiro Lacerda dos Santos; Luiz Carlos Gomes (Biological Invasions, 2024)

The natural anthraquinone dye emodin: Eco/genotoxicological characterization for aquatic organisms - Natália Oliveira de Farias; Amanda Rocha Rodrigues; Marina Tenório Botelho; Gabriel Rampazzo Magalhães; Riikka Räisänen; Harold S. Freeman; Gisela de Aragão Umbuzeiro (Food and Chemical Toxicology, 2024)

Cardiac hypertrophy that affects hyperthyroidism occurs independently of the NLRP3 inflammasome - Aline Cristina Parletta; Gabriela Cavazza Cerri; Claudia Ribeiro Borba Gasparini; Karine Panico; Denival Nascimento Vieira-Junior; Larissa Maria Zacarias-Rodrigues; Nathalia Senger; Amanda de Almeida Silva; Marina Fevereiro; Gabriela Placoná Diniz; Maria Cláudia Costa Irigoyen; Maria Luiza Morais Barreto-Chaves (Pflügers Archiv - European Journal of Physiology, 2024)

Assessment of toxicity of pyriproxyfen, Bacillus thuringiensis, and malathion and their mixtures used for mosquito control on embryo-larval development and behavior of zebrafish - Renata Meireles Oliveira Padilha; Samara da Silva Gomes; Jadson Freitas da Silva; Renatta Priscilla Ferreira Silva; André Lucas Corrêa de Andrade; Amanda Rodrigues dos Santos Magnabosco; Thamiris Pinheiro Santos; Andressa Raphaely de Lima Silva; Maria Leticia Santos Carnaúba da Silva; Marilia Ribeiro Sales Cadena; Pabyton Gonçalves Cadena (Environmental Science and Pollution Research, 2024)

Dynamic re-sedimentation of lacustrine carbonates in the Búzios Field, pre-salt section of Santos Basin, Brazil - Sabrina D. Altenhofen; Amanda G. Rodrigues; Leonardo Borghi; Luiz F. De Ros (Journal of South American Earth Sciences, 2024)

A longer period of epididymal sperm interaction with extender components during cryopreservation improves sperm quality, decreases the size of sperm distal cytoplasmic droplets, and changes the number of nanoparticles in the extender - Maria Alice de Almeida; Laura Gabrielli Haupenthal; Amanda Nespolo Silva; Gabriela Melendes Schneider; Paola Maria da Silva Rosa; André Furugen César de Andrade; Luciano Andrade Silva; Flávio Vieira Meirelles; Juliano Coelho da Silveira; Felipe Perecin; Maíra Bianchi Rodrigues Alves (Cryobiology, 2024)

Nitrospirillum viridazoti sp. nov., an Efficient Nitrogen-Fixing Species Isolated from Grasses - José Ivo Baldani; Natália dos Santos Ferreira; Stefan Shwab; Veronica Massena Reis; Luis Henrique de Barros Soares; Jean Luiz Simões-Araujo; Fernanda dos Santos Dourado; Evelise Bach; Natália Neutzling Camacho; Amanda Maura de Oliveira; Bruno José Rodrigues Alves; Andréia Loviane Silva; et al. (Current Microbiology, 2024)

Insights on the genomic diversity, virulence and resistance profile of a Campylobacter jejuni strain isolated from a hospitalized patient in Brazil - Carolina Nogueira Gomes; Miliane Rodrigues Frazão; Amanda Aparecida Seribelli; Dillon Oliver Reese Barker; Emily Victoria Che; Mara Corrêa Lelles Nogueira; Eduardo Napoleon Taboada; Juliana Pfrimer Falcão (Brazilian Journal of Microbiology, 2024)

Understanding the mechanism of action of protease inhibitors in controlling the growth of the Candida Genus: potential candidates for development of new antifungal molecules - Marciele Souza da Silva; Gabriel Bonan Taveira; Rodrigo da Silva Gebara; Layrana de Azevedo dos Santos; Milena Bellei Cherene; Thaynã Amanda Melo Souza; Felipe Figueirôa Moreira; Pedro Souto Rodrigues; Olney Vieira Motta; Sergio Henrique Seabra; André de Oliveira Carvalho; Rosana Rodrigues; et al. (Archives of Microbiology, 2024)

Immune response in paper wasp workers: Task matters more than age - Amanda Prato; Eduardo Fernando Santos; Helena Mendes Ferreira; Cintia Akemi Oi; Fábio Santos do Nascimento; Markus J. Rantala; Indrikis Krams; André Rodrigues de Souza (Journal of Insect Physiology, 2024)

Study of the stability of hydroelectrolytic sports beverages enriched with phenolic extract from jaboticaba peel or blueberry pulp - Thaís Caroline Buttow Rigolon; Larissa Lorrane Rodrigues Borges; Amanda Lais Alves Almeida Nascimento; Janaina Gonçalves Fernandes; João Carlos Bouzas Marins; Evandro Martins; Pedro Henrique Campelo; Paulo César Stringheta (Food and Humanity, 2024)

Zoonotic bacterial pathogens in bats samples around the world: a scoping review - Amanda Carvalho Rosado Ferreira; Raisa Abreu Bragança Colocho; Carine Rodrigues Pereira; Thallyta Maria Veira; Renato Gregorin; Andrey Pereira Lage; Elaine Maria Seles Dorneles (Preventive Veterinary Medicine, 2024)

The record of marine ingression in western Gondwana from Devonian conodonts in the Amazonas and Solimões basins, Brazil - Jordana Maria Viccari; Sara Nascimento; Ana Karina Scomazzon; Amanda Pericolo da Rosa; Andrés Felipe Rojas Mantilla; Sanmya Karolyne Rodrigues Dias; Paulo A. Souza; Valesca Brasil Lemos; Danielle Dall Amaria Soffiatti; Martín Andrés León Caffroni (Marine Micropaleontology, 2024)

Health of Holochilus chacarius (Rodentia: Cricetidae) in rice agroecosystem in a neotropical wetland assessed by histopathology - Amanda Costa Rodrigues; Érica Fernanda Gonçalves Gomes de Sá; Filipe Martins Santos; Nayara Yoshie Sano; Julia Gindri Bragato Pistori; Pedro Cordeiro-Estrela; Caio Lucca Cação Tognini Ozório; Heitor Miraglia Herrera; Gisele Braziliano de Andrade (Environmental Monitoring and Assessment, 2024)

Carbon storage and sequestration in a eucalyptus productive zone in the Brazilian Cerrado, using the Ca-Markov/Random Forest and InVEST models - Vitor Matheus Bacani; Bruno Henrique Machado da Silva; Amanda Ayumi de Souza Amede Sato; Bruna Dienifer Souza Sampaio; Elias Rodrigues da Cunha; Erivelton Pereira Vick; Víncler Fernandes Ribeiro de Oliveira; Hermiliano Felipe Decco (Journal of Cleaner Production, 2024)

Nutritional, chemical and functional potential of Inga laurina (Fabaceae): A barely used edible species - Amanda Medeiros Martins; Camila Rodrigues Adão Malafaia; Rafaela Machado Nunes; Anete Souza Mecenas; Patricia Homobono Britto De Moura; Michele Frazão Muzitano; Thelma de Barros Machado; Carla da Silva Carneiro; Ivana Correa Ramos Leal (Food Research International, 2024)

Exploring the effects of eugenol, menthol, and lidocaine as anesthetics on zebrafish glucose homeostasis - Gabriela Maressa Machado Baesso; Amanda Vitória Venâncio; Lívia Costa Varela Barca; Pepita Fernanda Peppi; Caique Aparecido Faria; João Pedro Cosmo Machado; Luiz David Solis Murgas; Álvaro José de Almeida Bicudo; Eduardo Maurício Mendes de Lima; André Rodrigues da Cunha Barreto-Vianna (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Corrigendum to ‘Multiple endpoints of polylactic acid biomicroplastic toxicity in adult zebrafish (Danio rerio)’ [Chemosphere, 277 (2021), 130279] - Thales Quintão Chagas; Ítalo Nascimento Freitas; Mateus Flores Montalvão; Rafael Henrique Nóbrega; Monica Rodrigues Ferreira Machado; Ives Charlie-Silva; Amanda Pereira da Costa Araújo; Abraão Tiago Batista Guimarães; Tenilce Gabriela da Silva Alvarez; Guilherme Malafaia (Chemosphere, 2024)

Meta-analysis of carbon stocks and biodiversity outcomes across Brazilian restored biomes - Catarina Jakovac; Katarzyna A. Korys; Aline F. Rodrigues; Amanda Ronix; Fernanda Tubenchlak; Lara M. Monteiro; Luisa Lemgruber; Herlle Souza Santos; Maiara Mendes; André B. Junqueira; Renato Crouzeilles; Veronica Maioli; et al. (Science of The Total Environment, 2024)

Conodonts paleobiogeographic dynamic of the Pennsylvanian epicontinental sea Itaituba-Piauí, in the northern intracratonic Brazilian basins, Western Gondwana - Sanmya Karolyne Rodrigues Dias; Andrés Felipe Rojas Mantilla; Martín Andrés Leon Caffroni; Ana Karina Scomazzon; Sara Nascimento; Amanda Pericolo da Rosa; Renato Sol Paiva de Medeiros; Paulo A. Souza; Afonso César Rodrigues Nogueira; Jordana Maria Viccari (Marine Micropaleontology, 2024)

Comparative toxicity of coal and coal ash: Assessing biological impacts and potential mechanisms through in vitro and in vivo testing - Fernanda B.M. Boaretto; Juliana da Silva; Amanda Scotti; Jayne S. Torres; Ana L.H. Garcia; Gabriela Z.P. Rodrigues; Günther Gehlen; Vinícios B. Rodrigues; Mariele F. Charão; Guilherme M. Soares; Johnny F. Dias; Jaqueline N. Picada (Journal of Trace Elements in Medicine and Biology, 2024)

Comparison of molecular techniques for the detection of Toxoplasma gondii in raw bovine milk from small rural properties in Brazil - Suzane Manzini; Thainá Valente Bertozzo; Isabella Neves Aires; Nássarah Jabur Lot Rodrigues; Amanda Bezerra Bertolini; Marcela Alexandrino; Jackieline Sampaio Steinle; Renata Pimentel Bandeira de Melo; Rinaldo Aparecido Mota; Maria Izabel Merino de Medeiros; Virgínia Bodelão Richini-Pereira; Vera Cláudia Lorenzetti Magalhães Curci; et al. (International Journal of Food Microbiology, 2024)

2,3,5-triiodobenzoic acid affects the in vitro propagation of Cedrela fissilis Vell. (Meliaceae) through alterations in endogenous polyamine and indol-3-acetic acid levels and the proteomic profile - Yrexam Rodrigues de Souza Ribeiro; Victor Paulo Mesquita Aragão; Renan Carrari-Santos; Kariane Rodrigues de Sousa; Amanda Ferreira Macedo; Eny Iochevet Segal Floh; Vanildo Silveira; Claudete Santa-Catarina (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Evaluation of the effect of sample suspension concentration and viral load on the outcome of the rabies tissue culture infection test - Tatiane de Cassia Pardo de Souza; Gilmara de Sousa e Silva; Willian de Oliveira Fahl; Adriana Candido Rodrigues; Karen Miyuki Asano; Karin Corrêa Scheffer; Enio Mori; Amanda Siena; Keila Iamamoto (Archives of Virology, 2024)

How did a tailings spill change the distribution of legacy organochlorine compounds in a Southeast Atlantic inner shelf area: Is a hidden danger being transferred to the ocean? - Ana Caroline Cabral; Amanda Câmara de Souza; Fabian Sá; Renato Rodrigues Neto; César C. Martins (Science of The Total Environment, 2023)

Exploring strategies to enhance anthocyanin bioavailability and bioaccessibility in food: A literature review - Amanda Lais Alves Almeida Nascimento; Larissa Lorrane Rodrigues Borges; Janaina Gonçalves Fernandes; Valdeir Viana Freitas; Evandro Martins; Pedro Henrique Campelo; Paulo Cesar Stringheta (Food Bioscience, 2023)

Lactococcus lactis subsp. lactis bv. diacetylactis Q5C6 strain as debittering adjunct culture for vegetable clotted cheese - Fabrizio Domenico Nicosia; Alessandra Pino; Amanda Vaccalluzzo; Vinícius Rodrigues Arruda Pinto; Andressa Fusieger; Rosita La Cava; Cinzia Caggia; Cinzia Randazzo; Antonio Fernandes de Carvalho (Food Bioscience, 2023)

Florivory on an alien tree as a potential case of biotic resistance provided by urban parrots - Paulo Antonio Silva; Larissa Lais Silva; Amanda Graciela Cherutte; Ana Caroline Silva Gomes; Lucilene Brito; Bruno Magro Rodrigues; Stephanie Teles Santos; Lucas Sobral Santos (Urban Ecosystems, 2023)

Virulence potential of Salmonella 1,4, [5],12:i:- strains isolated during decades from different sources in the Southeast region of Brazil - Giovana do Nascimento Pereira; Amanda Aparecida Seribelli; Carolina Nogueira Gomes; Felipe Pinheiro Vilela; Ludmilla Tonani; Monique Ribeiro Tiba-Casas; Marta Inês Cazentini Medeiros; Dália dos Prazeres Rodrigues; Márcia Regina von Zeska Kress; Juliana Pfrimer Falcão (Brazilian Journal of Microbiology, 2023)

Genetic diversity of adenovirus in neotropical bats from Brazil - Laís Santos Rizotto; Larissa Mayumi Bueno; Thaís Camilo Corrêa; Maria Vitória dos Santos de Moraes; Amanda de Oliveira Viana; Laura Morais Nascimento Silva; Julia Cristina Benassi; Guilherme Pereira Scagion; Bruna Larotonda Telezynski Lopes; Isabela Barbosa de Assis; Tatiana Ometto; Erick Gustavo Dorlass; et al. (Brazilian Journal of Microbiology, 2023)

Influence of spontaneous and inoculated fermentation of açai on simulated digestion, antioxidant capacity and cytotoxic activity - Amanda Lais Alves Almeida Nascimento; Mariane Sampaio da Silveira de Souza; Larissa Lorrane Rodrigues Borges; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Adriana Correa Mendonça; Luciana Azevedo; Mariana Araújo Vieira do Carmo; Amanda dos Santos Lima; Laura da Silva Cruz; Gabriel Abranches Dias Castro; Sergio Antonio Fernandes; et al. (Food Research International, 2023)

Utilization of Rosuvastatin and Endogenous Biomarkers in Evaluating the Impact of Ritlecitinib on BCRP, OATP1B1, and OAT3 Transporter Activity - Yeamin Huh; Anna Plotka; Hua Wei; Julia Kaplan; Nancy Raha; Justin Towner; Vivek S. Purohit; Martin E. Dowty; Robert Wolk; Manoli Vourvahis; Amanda King-Ahmad; Sumathy Mathialagan; et al. (Pharmaceutical Research, 2023)
Purpose Ritlecitinib, an inhibitor of Janus kinase 3 and tyrosine kinase expressed in hepatocellular carcinoma family kinases, is in development for inflammatory diseases. This study assessed the impact of ritlecitinib on drug transporters using a probe drug and endogenous biomarkers. Methods In vitro transporter-mediated substrate uptake and inhibition by ritlecitinib and its major metabolite were evaluated. Subsequently, a clinical drug interaction study was conducted in 12 healthy adult participants to assess the effect of ritlecitinib on pharmacokinetics of rosuvastatin, a substrate of breast cancer resistance protein (BCRP), organic anion transporting polypeptide 1B1 (OATP1B1), and organic anion transporter 3 (OAT3). Plasma concentrations of coproporphyrin I (CP-I) and pyridoxic acid (PDA) were assessed as endogenous biomarkers for OATP1B1 and OAT1/3 function, respectively. Results In vitro studies suggested that ritlecitinib can potentially inhibit BCRP, OATP1B1 and OAT1/3 based on regulatory cutoffs. In the subsequent clinical study, coadministration of ritlecitinib decreased rosuvastatin plasma exposure area under the curve from time 0 to infinity (AUC inf ) by ~ 13% and maximum concentration (C max ) by ~ 27% relative to rosuvastatin administered alone. Renal clearance was comparable in the absence and presence of ritlecitinib coadministration. PK parameters of AUC inf and C max for CP-I and PDA were also similar regardless of ritlecitinib coadministration. Conclusion Ritlecitinib does not inhibit BCRP, OATP1B1, and OAT3 and is unlikely to cause a clinically relevant interaction through these transporters. Furthermore, our findings add to the body of evidence supporting the utility of CP-I and PDA as endogenous biomarkers for assessment of OATP1B1 and OAT1/3 transporter activity.

Linking above and belowground carbon sequestration, soil organic matter properties, and soil health in Brazilian Atlantic Forest restoration - Wanderlei Bieluczyk; Fernanda Ometto Asselta; Deisi Navroski; Júlia Brandão Gontijo; Andressa Monteiro Venturini; Lucas William Mendes; Carla Penha Simon; Plínio Barbosa de Camargo; Amanda Maria Tadini; Ladislau Martin-Neto; José Albertino Bendassolli; Ricardo Ribeiro Rodrigues; et al. (Journal of Environmental Management, 2023)

A predatory social wasp does not avoid nestmates contaminated with a fungal biopesticide - André Rodrigues de Souza; Amanda Prato; Wilson Franca; Sircio Santos; Luan Dias Lima; Denise Araujo Alves; Rodrigo Cupertino Bernardes; Eduardo Fernando Santos; Fábio Santos do Nascimento; Maria Augusta Pereira Lima (Environmental Science and Pollution Research, 2023)

The Landscape of Neutralizing Monoclonal Antibodies (nAbs) for Treatment and Prevention of COVID-19 - Aline de Almeida Oliveira; Diana Praia Borges Freire; Ana Rodrigues de Andrade; Amanda de Miranda Marques; Luciana da Silva Madeira; José Procópio Moreno Senna; Ivna Alana Freitas Brasileiro da Silveira; Beatriz de Castro Fialho (Journal of Pharmaceutical Innovation, 2023)
Purpose After nearly 3 years of the COVID-19 pandemic, even though a vast body of knowledge and products (including vaccines and treatments) have been developed and disseminated, the virus is still evolving and new variants arising. Consequently, thousands of lives continue to be lost. Neutralizing monoclonal antibodies (nAbs) are promising drugs that emerged to treat SARS-CoV-2. In the uncertainty of the current situation, there is the question of whether organizations should continue to invest in this technology. To help decision-making in scientifical and pharmaceutical organizations, it is of major importance to monitor the development of products and technologies. Therefore, the aim of this study is analyze the landscape of nAbs for COVID-19. Methods The scenario of 473 biotherapeutics focusing on nAbs was evaluated using foresight techniques and a review of literature. Data were obtained from structured and semi-structured databases and processed for treatment, cleaning, consistency, validation, and enrichment. Results We identified 227 nAbs and performed an extensive literature review of 16 nAbs in late clinical development, including development technologies, responses to variants of concern (VOCs), manufacturing, and clinical aspects. Conclusions Even though the emergence of new VOCs is a threat to the effectiveness of this treatment, demanding constant genomic surveillance, the use of nAbs to treat and prevent COVID-19 will probably continue to be relevant due to excellent safety profiles and the possibility of immediate immunity transfer, especially in patients showing inadequate immunological response to vaccination. Therefore, we suggest that organizations should keep investing in improvements in this technology.

Pleural effusion-related Nocardia otitidiscaviarum, Anaplasma platys and Ehrlichia canis coinfection in a dog - Márcio Garcia Ribeiro; Carolina Polo Camargo da Silva; Larissa Marry Pchevuzinske; Fábio Vinícius Ramos Portilho; Amanda Keller Siqueira; Regina Kiomi Takahira; Natália Rodrigues Paschoal; Adriana Aparecida Lopes de Souza; Carolina Aparecida Rodrigues; Beatriz Oliveira de Almeida; Thaís Spessotto Bello; Marcelo Fagali Árabe Filho; et al. (Brazilian Journal of Microbiology, 2023)

Paleoenvironmental reconstruction of the Permian coal beds in the Paraná Basin (Brazil): evidence from organic geochemical and sedimentological analyses - Ricardo Maahs; Juliano Kuchle; Amanda Goulart Rodrigues; Taís Freitas da Silva; Marleny Blanco González; Fernando Erthal (Journal of South American Earth Sciences, 2023)

Structural, histochemical, and phytochemical characterization of Mikania cordifolia (L. f.) Willd. (Asteraceae) in a coastal dune environment - Angela M. Demétrio; Ana Claudia Rodrigues; Amanda Ellen de Athayde; Maique Weber Biavatti; Fernanda M. Cordeiro Oliveira; Flávio Lima Garcia; Makeli Garibotti Lusa (Flora, 2023)

The ecological role and potential impact of an alien tree highly attractive to native nectar-feeding birds in urban areas - Paulo Antonio Silva; Amanda Graciela Cherutte; Ana Caroline Silva Gomes; Larissa Lais Silva; Lucilene Brito; Bruno Magro Rodrigues; Pietro Kiyoshi Maruyama (Urban Ecosystems, 2023)

Biochemical characterization and assessment of leishmanicidal effects of a new L-amino acid oxidase from Crotalus durissus collilineatus snake venom (CollinLA AO-I) - Vitor de Freitas; Tássia Rafaella Costa; Amanda Rodrigues Nogueira; Lorena Polloni; Thales Alves de Melo Fernandes; Lucas Ian Veloso Correia; Bruna Cristina Borges; Samuel Cota Teixeira; Marcelo José Barbosa Silva; Fernanda Gobbi Amorim; Loïc Quinton; André Lopes Saraiva; et al. (Toxicon, 2023)

Molecular identification and antimicrobial resistance pattern of Nocardia isolated from 14 diseased dogs and cats - Larissa Anuska Zeni Condas; Marconi Rodrigues de Farias; Amanda Keller Siqueira; Tatiana Salerno; Kung Darh Chi; Juliana Werner; Agueda Castagna de Vargas; Guilherme Borges Bond; Tohru Gonoi; Tetsuhiro Matsuzawa; Márcio Garcia Ribeiro (Brazilian Journal of Microbiology, 2023)

Effects of using waste high-density polyethylene on the rheological, mechanical, and thermal performance of asphalt materials - Amanda Jessica Rodrigues da Silva; Adriano Elísio de Figueiredo Lopes Lucena; Osires de Medeiros Melo Neto; Ana Maria Gonçalves Duarte Mendonça; Daniel Beserra Costa; Robson Kel Batista de Lima (Environment, Development and Sustainability, 2023)

Multiple endpoints of polyethylene microplastics toxicity in vascular plants of freshwater ecosystems: A study involving Salvinia auriculata (Salviniaceae) - Alex Rodrigues Gomes; Ítalo Nascimento Freitas; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Amanda Pereira da Costa Araújo; Chinnaperumal Kamaraj; Md. Mostafizur Rahman; Abu Reza Md. Towfiqul Islam; Andrés Hugo Arias; Fábia Barbosa da Silva; Sengodan Karthi; Omar Cruz-Santiago; et al. (Journal of Hazardous Materials, 2023)

Single and joint toxic effects of thyroid hormone, levothyroxine, and amiodarone on embryo-larval stages of zebrafish (Danio rerio) - Thamiris Pinheiro Santos; Paulo Eduardo da Silva Bastos; Jadson Freitas da Silva; Stefânia Maria de Medeiros Vieira; Marília Cordeiro Galvão da Silva; André Lucas Corrêa de Andrade; Renata Meireles Oliveira Padilha; Amanda Rodrigues dos Santos Magnabosco; Marilia Ribeiro Sales Cadena; Pabyton Gonçalves Cadena (Ecotoxicology, 2023)

From wasted ferric sludge to valuable waste: a systematic review using the knowledge development process—constructivist method - Iana Chaiene de Araujo Vidal; Elisângela Maria Rodrigues Rocha; Arthur Marinho Cahino; Samara Teixeira Pereira; Amanda Gondim Cabral Quirino; Raqueline Caldas do Nascimento (Environment, Development and Sustainability, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Assessment of Health Risk and Presence of Metals in Water and Fish Samples from Doce River, Brazil, After Fundão Dam Collapse - Amanda Oliveira Mourão; Mayra Soares Santos; Alexandre Sylvio Vieira da Costa; Heberson Teixeira da Silva; Luiz Fernando Oliveira Maia; Márcia Cristina da Silva Faria; Mariandry del Vale Rodriguez Rodriguez; Jairo Lisboa Rodrigues (Archives of Environmental Contamination and Toxicology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Nutrient deficiency lowers photochemical and carboxylation efficiency in tobacco - Renan Falcioni; Thaise Moriwaki; Marlon Rodrigues; Karym Mayara de Oliveira; Renato Herrig Furlanetto; Amanda Silveira dos Reis; Glaucio Leboso Alemparte Abrantes dos Santos; Weslei Augusto Mendonça; Luis Guilherme Teixeira Crusiol; João Vitor Ferreira Gonçalves; Marcelo Luiz Chicati; Roney Berti de Oliveira; et al. (Theoretical and Experimental Plant Physiology, 2023)

Effect of experimental toothpaste containing hydroxyapatite nanoparticles and propolis, with and without fluoride, on the microcosm biofilm and enamel demineralization - Caroline Fernanda da Silva Ribeiro; Aline Dionizio; Tamara Teodoro Araújo; Chelsea Maria Vilas Boas Feitosa Rodrigues; Amanda Costa Mattos; Letícia Galli Otaviano; Larissa Tercília Grizzo; Ana Carolina Magalhães; Marília Afonso Rabelo Buzalaf (Biofouling, 2023)

Mapping the effects of Melinis minutiflora invasion on soil nitrogen dynamics in the Brazilian savanna: A dual-isotope approach - João Paulo Sena-Souza; Natália Lopes Rodovalho; Amanda Ferreira Andrade; José Roberto Rodrigues Pinto; Gabriela Bielefeld Nardoto (Pedobiologia, 2023)

Impact of different kernel grades on volatile compounds profile, fatty acids and oxidative quality of cashew nut oil - Amanda Rodrigues Leal; Ana Paula Dionísio; Fernando Antonio Pinto de Abreu; Gilleno Ferreira de Oliveira; Idila Maria da Silva Araújo; Hilton César Rodrigues Magalhães; Andressa Barbosa Leite; Emilly Kaiane Maia da Silva; Ronaldo Ferreira do Nascimento; Hélio Oliveira do Nascimento; Paulo Henrique Machado de Sousa (Food Research International, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Food safety concerns on polycyclic aromatic hydrocarbon contamination in fish products from estuarine bays throughout the American continent - Júlia Vianna de Pinho; Amanda P. Lopes; Paloma de Almeida Rodrigues; Rafaela Gomes Ferrari; Rachel Ann Hauser-Davis; Carlos Adam Conte-Junior (Science of The Total Environment, 2023)

RETRACTED: Toxicity assessment of SARS-CoV-2-derived peptides in combination with a mix of pollutants on zebrafish adults: A perspective study of behavioral, biometric, mutagenic, and biochemical toxicity - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Amanda Pereira da Costa Araújo; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Alex Rodrigues Gomes; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Andrés Hugo Arias; Davoodbasha Mubarak Ali; Chinnasamy Ragavendran; et al. (Science of The Total Environment, 2023)

Spectral method for macro and micronutrient prediction in soybean leaves using interval partial least squares regression - Glaucio Leboso Alemparte Abrantes dos Santos; Amanda Silveira Reis; Marcos Renan Besen; Renato Herrig Furlanetto; Marlon Rodrigues; Luís Guilherme Teixeira Crusiol; Karym Mayara de Oliveira; Renan Falcioni; Roney Berti de Oliveira; Marcelo Augusto Batista; Marcos Rafael Nanni (European Journal of Agronomy, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

Trichoderma as a powerful fungal disease control agent for a more sustainable and healthy agriculture: recent studies and molecular insights - Amanda O. Rodrigues; Louise L. May De Mio; Carlos R. Soccol (Planta, 2023)

Local administration of curcumin-loaded nanoparticles enhances periodontal repair in vivo - Cindy Grace Perez-Pacheco; Natalie Aparecida Rodrigues Fernandes; Angelo Constantino Camilli; Danilo Paschoal Ferrarezi; Amanda Favoreto Silva; Mayara Cristina Zunareli; Camila Fernanda Amantino; Fernando Lucas Primo; Morgana Rodrigues Guimarães-Stabilli; Carlos Rossa Junior (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

N-acetylation of toxic aromatic amines by fungi: Strain screening, cytotoxicity and genotoxicity evaluation, and application in bioremediation of 3,4-dichloroaniline - Amanda Dal’Ongaro Rodrigues; Arthur dos Santos Montanholi; Angela Akimi Shimabukuro; Murilo Kioshi Aquino Yonekawa; Nadla Soares Cassemiro; Denise Brentan Silva; Clarice Rossato Marchetti; Carlos Eduardo Weirich; Adilson Beatriz; Fabiana Fonseca Zanoelo; Maria Rita Marques; Giovana Cristina Giannesi; et al. (Journal of Hazardous Materials, 2023)

Cardanol in the feeding of meat-type quail breeders - Amanda Karen Santos Rocha; Ednardo Rodrigues Freitas; Rafael Carlos Nepomuceno; Thalles Ribeiro Gomes; Valquíria Sousa Silva; Rithiele Dantas dos Santos; Luana Ledz Costa Vasconcelos Rocha; Cirliane de Abreu Freitas; Maria Teresa Salles Trevisan (Tropical Animal Health and Production, 2022)

Testosterone nanoemulsion produced masculinized Nile tilapia (Oreochromis niloticus) - Amanda Rodrigues dos Santos Magnabosco; Ester Inácio Damião Quinova; Matheus Victor Viana de Melo; Paulo Eduardo da Silva Bastos; Thamiris Pinheiro Santos; Ivanildo Inácio da Silva Júnior; André Lucas Corrêa de Andrade; Renata Meireles Oliveira Padilha; Jadson Freitas da Silva; Fabrício Bezerra de Sá; Marília Ribeiro Sales Cadena; Pabyton Gonçalves Cadena (Fish Physiology and Biochemistry, 2022)

Effect of three commercial algaecides on cyanobacteria and microcystin-LR: implications for drinking water treatment using activated carbon - Amanda Sati Hirooka Koshigoe; Vinicíus Diniz; Caio Rodrigues-Silva; Davi Gasparini Fernandes Cunha (Environmental Science and Pollution Research, 2022)

Are echocardiographic parameters affected by body condition scores in blue-fronted Amazon parrots (Amazona aestiva, Linnaeus, 1758)? - Gisele Junqueira dos Santos; Amanda Sarita Cruz Aleixo; Alícia Giolo Hippólito; Barbara Sardela Ferro; Priscylla Tatiana Chalfun Guimarães Okamoto; Maria Lucia Gomes Lourenço; Vania Maria de Vasconcelos Machado; Paulo Roberto Rodrigues Ramos; Sheila Canevese Rahal; Carlos Roberto Teixeira; Alessandra Melchert (Veterinary Research Communications, 2022)

Co-production of Classes A and B Carbapenemases BKC-1 and VIM-2 in a Clinical Pseudomonas Putida Group Isolate from Brazil - Amanda Yaeko Yamada; Andreia Rodrigues de Souza; Marisa de Jesus de Castro Lima; Alex Domingos Reis; Karoline Rodrigues Campos; Amanda Maria de Jesus Bertani; Leonardo Jose Tadeu de Araujo; Claudio Tavares Sacchi; Monique Ribeiro Tiba-Casas; Carlos Henrique Camargo (Current Microbiology, 2022)

The mesoionic compound MI-D changes energy metabolism and induces apoptosis in T98G glioma cells - Marília Locatelli Corrêa-Ferreira; Amanda do Rocio Andrade Pires; Igor Resendes Barbosa; Aurea Echevarria; Guilherme Henrique Pedrassoli; Sheila Maria Brochado Winnischofer; Guilhermina Rodrigues Noleto; Sílvia Maria Suter Correia Cadena (Molecular and Cellular Biochemistry, 2022)

The association of extracts of Achyrocline satureioides and the fungus Beauveria bassiana against the tick Rhipicephalus microplus - Rafaela Regina Fantatto; Yousmel Alemán Gainza; Amanda Figueiredo; Rodrigo Sorrechia; Ana Carolina de Souza Chagas; Rosemeire Cristina Linhari Rodrigue Pietro (Experimental and Applied Acarology, 2022)

Solvent screening, optimization and kinetic parameters of the biocatalytic epoxidation reaction of β-pinene mediated by Novozym®435 - Gustavo dos Santos Martins; Amanda Staudt; Felipe Korbus Sutili; Camila Rodrigues Adão Malafaia; Ivana Correa Ramos Leal (Biotechnology Letters, 2022)

Lung-Brain Crosstalk in Sepsis: Protective Effect of Prophylactic Physical Exercise Against Inflammation and Oxidative Stress in Rats - Amanda Della Giustina; Judite Filgueiras Rodrigues; Erick Bagio; Sandra Bonfante; Larissa Joaquim; Graciela Zarbato; Solange Stork; Richard Simon Machado; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Khiany Mathias; Carlos Dacoregio; et al. (Molecular Neurobiology, 2022)

Morphophysiological Changes in Genipa americana Seedlings in Response to Root Deformation and Substrate Attributes - Catriane Sousa-Santos; Amanda Freitas Cerqueira; Ândrea Carla Dalmolin; Álvaro Alves de Almeida; Martielly Santana dos Santos; Natanielly Rodrigues Avelino; Roberta Barreto dos Santos; José Olímpio de Souza Júnior; Marcelo Schramm Mielke (Journal of Soil Science and Plant Nutrition, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Effects of the plant growth regulators, cobalt and molybdenum on the physiology of ‘Crimson Seedless’ grapevines - Amanda Cristina Esteves Amaro Baron; Daniel Baron; Essione Ribeiro Souza; Laíse Sousa Moreira; Elizabeth Orika Ono; João Domingos Rodrigues (Acta Physiologiae Plantarum, 2022)

Correction to: Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Assessing phosphorus nutritional status in maize plants using leaf-based hyperspectral measurements and multivariate analysis - Karym Mayara de Oliveira; Renato Herrig Furlanetto; Marlon Rodrigues; Glaucio Leboso Alemparte Abrantes dos Santos; Amanda Silveira Reis; Luís Guilherme Teixeira Crusiol; Marcos Rafael Nanni; Everson Cezar; Roney Berti de Oliveira (International Journal of Remote Sensing, 2022)

Drivers of fish trophic guild composition in lakes of the Upper Paraná River floodplain - Taise Miranda Lopes; Carolina Mendes Muniz; Marcelo Henrique Schmitz; Rosa Maria Dias; Amanda Cantarute Rodrigues; Matheus Gimenez Buzo; Edivando Vitor do Couto; Angelo Antonio Agostinho (Aquatic Sciences, 2022)

Klebsiella-induced infections in domestic species: a case-series study in 697 animals (1997–2019) - Márcio Garcia Ribeiro; Amanda Bonalume Cordeiro de Morais; Ana Carolina Alves; Carmen Alicia Daza Bolaños; Carolina Lechinski de Paula; Fábio Vinicius Ramos Portilho; Geraldo de Nardi Júnior; Gustavo Henrique Batista Lara; Lorrayne de Souza Araújo Martins; Lucieny Sierra Moraes; Rafaela Mastrangelo Risseti; Simony Trevizan Guerra; et al. (Brazilian Journal of Microbiology, 2022)

Productive characteristics of feedlot Santa Inês and Dorper lambs: intake, digestibility, feeding behavior, performance, carcass traits, and meat quality - Rodrigo Brito Saldanha; Luis Gabriel Alves Cirne; Lara Maria Santos Brant; Carlindo Santos Rodrigues; Douglas dos Santos Pina; Susiane de Carvalho Matos; Amanda Bastos Grimaldi; Silvia Cheles Bento; Manuela Silva Libânio Tosto; Stefanie Alvarenga Santos; Henry Daniel Ruiz Alba; Gleidson Giordano Pinto de Carvalho (Tropical Animal Health and Production, 2022)

Association between high-risk pregnancy and environmental contaminants in the Metropolitan Region of Baixada Santista, Brazil - Joice Maria Pacheco Antonio Fernandes; Ysabely de Aguiar Pontes Pamplona; Jhonnes Alberto Vaz; Amanda Rodrigues Pereira; Carolina Luísa Alves Barbieri; Alfésio Luís Ferreira Braga; Lourdes Conceição Martins (Environmental Science and Pollution Research, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Involvement of differentially accumulated proteins and endogenous auxin in adventitious root formation in micropropagated shoot cuttings of Cedrela fissilis Vellozo (Meliaceae) - Yrexam Rodrigues de Souza Ribeiro; Victor Paulo Mesquita Aragão; Kariane Rodrigues de Sousa; Amanda Ferreira Macedo; Eny Iochevet Segal Floh; Vanildo Silveira; Claudete Santa‑Catarina (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Helicobacter pylori virulence dupA gene: risk factor or protective factor? - Lucas Luiz de Lima Silva; Ana Karoline Silva Oliveira; Aline Rodrigues Gama; Amanda Ferreira Paes Landim Ramos; Antonio Márcio Teodoro Cordeiro Silva; Angel José Vieira Blanco; José Daniel Gonçalves Vieira; Lucas Trevizani Rasmussem; Lilian Carla Carneiro; Mônica Santiago Barbosa (Brazilian Journal of Microbiology, 2021)

Virulence Genes Profile and Antimicrobial Susceptibility of Community-Acquired Bacterial Urinary Tract Infections in a Brazilian Hospital - Fernanda Morcatti Coura; Vitoria Marra de Souza Savini; Rafael Gariglio Clark Xavier; Carolina Pantuzza Ramos; Rodrigo Otávio Silveira Silva; Marcos Bryan Heinemann; Andrea Micke Moreno; Terezinha Knöbl; Elaine Maria Seles Dorneles; Dirceia Aparecida da Costa Custódio; Carine Rodrigues Pereira; Pedro Felipe Rodrigues e Oliveira; et al. (Current Microbiology, 2021)

Gonadal morphology and difference in reproductive development of two isolated populations of Astyanax rivularis ( T eleostei, C haracidae) - Patricia Postingel Quirino; Diógenes Henrique de Siqueira‐Silva; Maira da Silva Rodrigues; Amanda Pereira dos Santos‐Silva; Maria Luiza Ribeiro Delgado; José Augusto Senhorini; Alexandre Ninhaus‐Silveira; Rosicleire Veríssimo‐Silveira (Journal of Fish Biology, 2021)
Individuals of the same species may present different reproductive tactics depending on the environment in which they develop and mature. The present study aimed to define the gonadal development phases of males and females of Astyanax rivularis and to carry out a comparative analysis of the reproductive development of specimens captured in two isolated environments of the São Francisco River basin in Serra da Canastra, Brazil (Point 1: low vegetation and river showing calm and crystalline waters with small well formations; Point 2: current waters, and well‐established areas of arboreal vegetation). Thus, the gonads of A. rivularis specimens were collected, fixed and processed with techniques for light microscopy. Five maturation phases of the females' reproductive cycle were established: immature, developing, spawning capable, regressing and regenerating. Three maturation phases of the males' reproductive cycle were observed: spawning capable, regressing, and regenerating. There are differences in the phases of gonadal development of A. rivularis between the two sampling points so that, possibly, animals upstream of the waterfall demonstrate a delay in the reproductive cycle in relation to animals downstream.

Chemical, physical, and biological attributes in soils affected by deposition of iron ore tailings from the Fundão Dam failure - Aline Oliveira Silva; Amanda Azarias Guimarães; Bruna Daniela Ortiz Lopez; Carin Sgobi Zanchi; Cesar Florentino Puma Vega; Éder Rodrigues Batista; Fatima Maria de Souza Moreira; Flávia Romam da Costa Souza; Flávio Araújo Pinto; Jessé Valentim dos Santos; Joana Junqueira Carneiro; José Oswaldo Siqueira; et al. (Environmental Monitoring and Assessment, 2021)

Maclura tinctoria Extracts: In Vitro Antibacterial Activity against Aeromonas hydrophila and Sedative Effect in Rhamdia quelen - Luana da Costa Pires; Patricia Rodrigues; Quelen Iane Garlet; Luisa Barichello Barbosa; Bibiana Petri da Silveira; Guerino Bandeira Junior; Lenise de Lima Silva; Amanda Gindri; Rodrigo Coldebella; Cristiane Pedrazzi; Agueda Palmira Castagna de Vargas; Bernardo Baldisserotto; et al. (Fishes, 2021)
Maclura tinctoria is a tree species native from Brazil and rich in phenolic compounds. Since plant antibacterial activity is highly associated with phenolic compound concentration, we aim to evaluate the in vitro antimicrobial activity of different extracts against fish pathogenic bacteria. In addition, some phenolic compounds have central depressant effects and can be useful in aquaculture due to possible sedative and/or anesthetic effects. Four M. tinctoria extracts were extracted separately with ethanol; leaves (LE), bark (BE), heartwood (HE), and the sapwood (SE). In vitro antimicrobial activity was tested against Aeromonas strains at concentrations of 6400 to 3.125 μg/mL. The sedative effect was evaluated for 24 h with 30 and 100 mg/L concentrations. Chemical composition was analyzed by HPLC-DAD-MS. The HE extract had the best MIC (400 µg/mL) and MBC (800 µg/mL) compared to the LE, BE, and SE extracts. LE extract induced deep sedation and the BE, SE, and HE extracts induced light sedation. Additionally, BE, SE, and HE induced a normal behavior without side effects. Polyphenolic compounds with antimicrobial activity and sedative effects were identified mainly in HE. Thus, HE extract is safe and can be used as a sedative for silver catfish.

Selection of new sweet potato genotypes based on production parameters, physical root characteristics and resistance to Euscepes postfasciatus - Murilo Henrique Souza Leal; André Ricardo Zeist; Nilson Rodrigues Júnior; André Dutra Silva Júnior; José Henrique Verhalem Arantes; Jair Garcia Neto; Julia Roberta Sanches de Pieri; Amanda Carvalho Perrud (Journal of Crop Science and Biotechnology, 2021)

Identification of enzyme inhibitors and antimicrobial activities from Capsicum annuum L. protein extracts against Colletotrichum scovillei - Lídia Da Silva Pereira; Thaynã Amanda Melo Souza; Rafael Walter; Cláudia Pombo Sudré; Layrana De Azevedo Dos Santos; Álan Chrisley Maracahipes; Gabriel Bonan Taveira; Virginia Silva Carvalho; Celso Shiniti Nagano; Renata Pinheiro Chaves; Rosana Rodrigues; André De Oliveira Carvalho; et al. (Horticulture, Environment, and Biotechnology, 2021)

The invasion of an alien characiform fish and the decline of a native congener in a Neotropical river-floodplain system - Maria Julia Mileo Ganassin; Emili García-Berthou; Amanda Cantarute Rodrigues; Carolina Pedrozo do Nascimento; Carolina Mendes Muniz; Matheus Tenório Baumgartner; Marcelo Henrique Schmitz; Luiz Carlos Gomes (Hydrobiologia, 2021)

Bacteriological, cytological, and molecular investigation of Corynebacterium pseudotuberculosis, mycobacteria, and other bacteria in caseous lymphadenitis and healthy lymph nodes of slaughtered sheep - Thiago de Oliveira Zamprogna; Dayana Ribeiro; Vasco A.C. Azevedo; Gustavo Henrique Batista Lara; Rodrigo Garcia Motta; Rodrigo Costa da Silva; Amanda Keller Siqueira; Geraldo de Nardi Júnior; Fernando José Paganini Listoni; Lorrayne de Souza Araújo Martins; Aristeu Vieira da Silva; Fábio Vinícius Ramos Portilho; et al. (Brazilian Journal of Microbiology, 2021)

Mining Co-products as Sources of Multi-nutrients for Cultivation of Brachiaria ruziziensis - Marlon Rodrigues; Marcos Rafael Nanni; Carlos Augusto Posser Silveira; Everson Cezar; Glaucio Leboso Alemparte Abrantes dos Santo; Renato Herrig Furlanetto; Karym Mayara de Oliveira; Amanda Silveira Reis (Natural Resources Research, 2021)

A high number of multidrug-resistant and predominant genetically related cluster of Shigella flexneri strains isolated over 34 years in Brazil - Júlia Cunha Gonzales; Amanda Aparecida Seribelli; Carolina Nogueira Gomes; Dália dos Prazeres Rodrigues; Fábio Campioni; Jaqueline Passaglia; Paulo da Silva; Juliana Pfrimer Falcão (Brazilian Journal of Microbiology, 2020)

Inoculation with the endophytic bacterium Herbaspirillum seropedicae promotes growth, nutrient uptake and photosynthetic efficiency in rice - Alessandro C. Ramos; Juliana Melo; Sávio B. de Souza; Amanda A. Bertolazi; Renderson A. Silva; Weverton P. Rodrigues; Eliemar Campostrini; Fábio L. Olivares; Frederico J. Eutrópio; Cristina Cruz; Teresa Dias (Planta, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Transparent polyethylene covering film in tropical grapevines does not alter photosynthesis, plant growth, fruit quality or yield - Luciana Venturotti Braun de Almeida; Weverton Pereira Rodrigues; Jefferson Rangel da Silva; Fábio Afonso Mazzei Moura de Assis Figueiredo; Bruna Côrrea da Silva de Deus; Katherine Fraga Ruas; Tiago Massi Ferraz; Amanda de Oliveira Martins; Kevin Lee Griffin; Ricardo Bressan-Smith; Eliemar Campostrini (Theoretical and Experimental Plant Physiology, 2020)

Lower cost alternatives for molecular diagnosis of COVID-19: conventional RT-PCR and SYBR Green-based RT-qPCR - Erick Gustavo Dorlass; Cairo Oliveira Monteiro; Amanda Oliveira Viana; Camila Pereira Soares; Rafael Rahal Guaragna Machado; Luciano Matsumiya Thomazelli; Danielle Bastos Araujo; Fabyano Bruno Leal; Erika Donizette Candido; Bruna Larotonda Telezynski; Camila Araujo Valério; Vanessa Nascimento Chalup; et al. (Brazilian Journal of Microbiology, 2020)

Functionally redundant communities do not show differences in the main environmental drivers of different diversity metrics - Amanda Cantarute Rodrigues; Natália Carneiro Lacerda dos Santos; Luiz Carlos Gomes (Aquatic Sciences, 2020)

Reproductive biology of Prepusa hookeriana (Gentianaceae): an endangered species of high-altitude grasslands in Brazil - Ana Luisa Lemos; Marina Muniz Moreira; Cristine Rodrigues Benevides; Amanda Soares Miranda; Ana Tereza Araújo Rodarte; Heloisa Alves de Lima (Brazilian Journal of Botany, 2020)

Gastroenteric Viruses Detection in a Drinking Water Distribution-to-Consumption System in a Low-Income Community in Rio de Janeiro - Marize Pereira Miagostovich; Mônica Simões Rocha; Fabiane Bertoni dos Reis; Marcelo Santos Sampaio; Renata de Saldanha da Gama Gracie Carrijo; Fabio Correia Malta; Janaína Rodrigues; Amanda Genuino; Matheus Ribeiro da Silva Assis; Tulio Machado Fumian; Paulo Rubens Guimarães Barrocas (Food and Environmental Virology, 2020)

Development of a novel anti-biofilm peptide derived from profilin of Spodoptera frugiperda - Amanda Carolina Borges da Silva; Janaina de Cassia Orlandi Sardi; Daniella Gorete Lourenço de Oliveira; Caio Fernando Ramalho de Oliveira; Helder Freitas dos Santos; Edson Lucas dos Santos; Edson Crusca; Marlon Henrique Cardoso; Octávio Luiz Franco; Maria Lígia Rodrigues Macedo (Biofouling, 2020)

Identification of genes from the general phenylpropanoid and monolignol-specific metabolism in two sugarcane lignin-contrasting genotypes - Douglas Jardim-Messeder; Tatiane da Franca Silva; Jose Pedro Fonseca; José Nicomedes Junior; Lucia Barzilai; Thais Felix-Cordeiro; Joyce Carvalho Pereira; Clara Rodrigues-Ferreira; Isabela Bastos; Tereza Cristina da Silva; Vinicius de Abreu Waldow; Daniela Cassol; et al. (Molecular Genetics and Genomics, 2020)

Phylogenetic analysis revealed that Salmonella Typhimurium ST313 isolated from humans and food in Brazil presented a high genomic similarity - Amanda Ap. Seribelli; Júlia C. Gonzales; Fernanda de Almeida; Leandro Benevides; Marta I. Cazentini Medeiros; Dália dos Prazeres Rodrigues; Siomar de C. Soares; Marc W. Allard; Juliana P. Falcão (Brazilian Journal of Microbiology, 2020)

Physiological effects of strobilurin and carboxamides on plants: an overview - Amanda Cristina Esteves Amaro; Daniel Baron; Elizabeth Orika Ono; João Domingos Rodrigues (Acta Physiologiae Plantarum, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Use of bean meal (Phaseolus vulgaris L.) in goat rations for meat production - Milenna Alves dos Santos; Amanda Estefanir Cordeiro; Dielen Janaira Menezes da Silva; Mario Adriano Avila Queiroz; Glayciane Costa Gois; Daniel Ribeiro Menezes; Salete Alves de Moraes; Tadeu Vinhas Voltolini; Karina Costa Busato; Rafael Torres de Souza Rodrigues (Tropical Animal Health and Production, 2019)

Degradation of haloacetic acids with the Fenton-like and analysis by GC-MS: use of bioassays for monitoring of genotoxic, mutagenic and cytotoxic effects - Amanda Oliveira Mourão; Diego Francis Silva; Mariandry Rodriguez; Thamyris Souza Torres; Elton Santos Franco; Valter Lúcio Pádua; Márcia Cristina da Silva Faria; Luiz Fernando Oliveira Maia; Jairo Lisboa Rodrigues (Environmental Monitoring and Assessment, 2019)

Thyroxine, levothyroxine, and thyroxine complexed into cyclodextrin changed animal behavior, oxygen consumption, and photopic electroretinogram of Colossoma macropomum - Thamiris Pinheiro Santos; Priscila Rafaela Leão Soares; Marília Cordeiro Galvão da Silva; Stephannie Caroline Barros Lucas da Silva; André Lucas Correa de Andrade; Amanda Rodrigues dos Santos; Jadson Freitas da Silva; Elyda Grazyelle da Silva Oliveira; Elton Hugo Lima da Silva Souza; Fabrício Bezerra de Sá; Marilia Ribeiro Sales Cadena; Pabyton Gonçalves Cadena (Fish Physiology and Biochemistry, 2019)

Environmental and geographic distance determining fish assemblage similarity in a floodplain: role of flow and macrophyte presence - Rafaela Vendrametto Granzotti; Ragna Woeltje Tavares; Amanda Cantarute Rodrigues; Taise Miranda Lopes; Luiz Carlos Gomes (Environmental Biology of Fishes, 2019)

Evaluation of Tagetes patula (Asteraceae) as an ecological alternative in the search for natural control of the cattle tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Flávio Augusto Sanches Politi; Rafaela Regina Fantatto; Alexander Alves da Silva; Isabela Jacob Moro; Bruno Rodrigues Sampieri; Maria Izabel Camargo-Mathias; Amanda Figueiredo; Ana Carolina de Souza Chagas; Maysa Furlan (Experimental and Applied Acarology, 2019)

Sub-lethal effects induced by a mixture of different pharmaceutical drugs in predicted environmentally relevant concentrations on Lithobates catesbeianus (Shaw, 1802) (Anura, ranidae) tadpoles - Diogo Ferreira do Amaral; Mateus Flores Montalvão; Bruna de Oliveira Mendes; Amanda Pereira da Costa Araújo; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Environmental Science and Pollution Research, 2019)

In Vitro Characterization of Lactobacillus Strains Isolated from Fruit Processing By-Products as Potential Probiotics - Thatyane Mariano Rodrigues de Albuquerque; Estefânia Fernandes Garcia; Amanda de Oliveira Araújo; Marciane Magnani; Maria Saarela; Evandro Leite de Souza (Probiotics and Antimicrobial Proteins, 2018)

Surviving in hot and cold: psychrophiles and thermophiles from Deception Island volcano, Antarctica - Amanda G. Bendia; Gabriel G. Araujo; André A. Pulschen; Bruna Contro; Rubens T. D. Duarte; Fábio Rodrigues; Douglas Galante; Vivian H. Pellizari (Extremophiles, 2018)

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Antibacterial activity of extract and fractions from branches of Protium spruceanum and cytotoxicity on fibroblasts - Tatiane Roquete Amparo; Ivanildes Vasconcelos Rodrigues; Janaína Brandão Seibert; Rafaella Hilda Zaniti Souza; Amanda Ribeiro de Oliveira; Vivette Appolinário Rodrigues Cabral; Paula Melo de Abreu Vieira; Geraldo Célio Brandão; Adriana Akemi Okuma; Sidney Augusto Vieira Filho; Luiz Fernando Medeiros Teixeira; Gustavo Henrique Bianco de Souza (Natural Product Research, 2018)

Coexistence between native and nonnative species: the invasion process and adjustments in distribution through time for congeneric piranhas in a Neotropical floodplain - Amanda Cantarute Rodrigues; Herick Soares de Santana; Matheus Tenório Baumgartner; Luiz Carlos Gomes (Hydrobiologia, 2018)

Bradyrhizobium forestalis sp. nov., an efficient nitrogen-fixing bacterium isolated from nodules of forest legume species in the Amazon - Elaine Martins da Costa; Amanda Azarias Guimarães; Teotonio Soares de Carvalho; Tainara Louzada Rodrigues; Paula Rose de Almeida Ribeiro; Liesbeth Lebbe; Anne Willems; Fatima M. de Souza Moreira (Archives of Microbiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Kinetic and thermodynamic parameters, and partial characterization of the crude extract of tannase produced by Saccharomyces cerevisiae CCMB 520 - Lúzia Morgana de Melo Lopes; Larissa Hayannyelly Costa Batista; Marcos Juliano Gouveia; Tonny Cley Campos Leite; Marcelo Rodrigues Figueira de Mello; Sandra Aparecida de Assis; Amanda Reges de Sena (Natural Product Research, 2018)

Development of Cleruchoides noackae, an egg-parasitoid of Thaumastocoris peregrinus, in eggs laid on different substrates, with different ages and post-cold storage - Leonardo Rodrigues Barbosa; Ângelo Peruffo Rodrigues; Lohana Neves de Souza; Luís Amilton Foerster; Amanda Rodrigues de Souza; Bárbara Monteiro de Castro e Castro; Carlos Frederico Wilcken; José Cola Zanuncio (BioControl, 2018)

Antimicrobial activity and acute toxicity of ozonated lomefloxacin solution - Amanda Marchi Duarte de Oliveira; Milena Guedes Maniero; Caio Rodrigues-Silva; José Roberto Guimarães (Environmental Science and Pollution Research, 2017)

Polyamine, amino acid, and carbohydrate profiles during seed storage of threatened woody species of the Brazilian Atlantic Forest may be associated with seed viability maintenance - Kariane Rodrigues Sousa; Victor Paulo Mesquita Aragão; Ricardo Souza Reis; Amanda Ferreira Macedo; Henrique Duarte Vieira; Cláudio Luiz Melo de Souza; Eny Iochevet Segal Floh; Vanildo Silveira; Claudete Santa-Catarina (Brazilian Journal of Botany, 2016)

Cadmium and lead in seafood from the Aratu Bay, Brazil and the human health risk assessment - Cecilia Freitas Silva da Araújo; Mariângela Vieira Lopes; Mirian Rocha Vasquez; Thiago Santos Porcino; Amanda Santos Vaz Ribeiro; Juliana Lima Gomes Rodrigues; Sérgio Soares do Prado Oliveira; José Antonio Menezes-Filho (Environmental Monitoring and Assessment, 2016)

In vitro organogenesis of Cedrela fissilis Vell. (Meliaceae): the involvement of endogenous polyamines and carbohydrates on shoot development - Victor Paulo Mesquita Aragão; Yrexam Rodrigues de Souza Ribeiro; Ricardo Souza Reis; Amanda Ferreira Macedo; Eny Iochevet Segal Floh; Vanildo Silveira; Claudete Santa-Catarina (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Environmental Surveillance of Polioviruses in Rio de Janeiro, Brazil, in Support to the Activities of Global Polio Eradication Initiative - Joseane Simone de Oliveira Pereira; Lidiane Rodrigues da Silva; Amanda de Meireles Nunes; Silas de Souza Oliveira; Eliane Veiga da Costa; Edson Elias da Silva (Food and Environmental Virology, 2016)

Erratum to: Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Amanda Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

The use of grafting to improve the net photosynthesis of cucumber - Amanda Cristina Esteves Amaro; Ana Claudia Macedo; Anamaria Ribeiro Pereira Ramos; Rumy Goto; Elizabeth Orika Ono; João Domingos Rodrigues (Theoretical and Experimental Plant Physiology, 2014)

Anti-nociceptive and anti-inflammatory activities of (−)-α-bisabolol in rodents - Nayrton Flávio Moura Rocha; Emiliano Ricardo Vasconcelos Rios; Alyne Mara Rodrigues Carvalho; Gilberto Santos Cerqueira; Amanda de Araújo Lopes; Luzia Kalyne Almeida Moreira Leal; Marília Leite Dias; Damião Pergentino de Sousa; Francisca Cléa Florenço de Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Combination Efficacy of Voriconazole and Amphotericin B in the Experimental Disease in Immunodeficient Mice Caused by Fluconazole-resistant Cryptococcus neoformans - Eriques Gonçalves Silva; Claudete Rodrigues Paula; Amanda Latercia Tranches Dias; Marilene Rodrigues Chang; Luciana da Silva Ruiz; Valderez Gambale; Renato Araujo Prates; Martha Simões Ribeiro (Mycopathologia, 2011)